Surface Protection Film
Patent Information
- Application Number
- JP2021096246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2021-06-09
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-10-15
AI Technical Summary
【0015】 本発明によれば、代表的には、光学部材や電子部材の製造工程において、加工、組立、検査、輸送などの際の該光学部材や該電子部材の表面の傷付き防止のために該光学部材や該電子部材の露出面に貼着される、粘着剤層を含む表面保護フィルムであって、剥離帯電圧を十分に抑制し、剥離時に該光学部材や該電子部材を破損しない表面保護フィルムを提供できる。
Smart Images

Figure 0007638796000007 
Figure 0007638796000001 
Figure 0007638796000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface protection film. [Background technology]
[0002] In the manufacturing process of optical and electronic components, a surface protective film is generally applied to the exposed surface of the optical and electronic components to prevent the surfaces of the optical and electronic components from being damaged during processing, assembly, inspection, transportation, etc. Such a surface protective film is peeled off from the optical and electronic components when surface protection is no longer necessary (Patent Document 1).
[0003] Usually, surface protection films, optical components, and electronic components have high electrical insulation and generate static electricity due to friction or peeling. Therefore, static electricity is likely to be generated when peeling off a surface protection film from an optical component or electronic component. In such a case, for example, if a voltage is applied to the liquid crystal while static electricity remains, there is a concern that the orientation of the liquid crystal molecules may be lost or the panel may be damaged. In addition, the presence of static electricity may attract dust or reduce workability.
[0004] In order to prevent static electricity, surface protection films are subjected to antistatic treatment. For example, it has been reported that antistatic functions are imparted by forming an antistatic layer or applying an antistatic coating as the surface layer (top coat layer, back layer) of the surface protection film (Patent Documents 2 and 3).
[0005] Furthermore, in order to impart antistatic properties to the adhesive layer itself that constitutes the surface protection film, a method has been used in which an ionic compound such as an alkali metal salt or an ionic liquid that functions as an antistatic agent is incorporated into the adhesive layer and then transferred to the adherend (Patent Document 4). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-17109 A [Patent Document 2] JP 2004-223923 A [Patent Document 3] JP 2008-255332 A [Patent Document 4] Japanese Patent Application Publication No. 9-165460 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a surface protection film including a pressure-sensitive adhesive layer that is attached to an exposed surface of an optical component or electronic component to prevent the surface of the optical component or electronic component from being scratched during processing, assembly, inspection, transportation, etc., typically in the manufacturing process of the optical component or electronic component, and that sufficiently suppresses peeling electrification voltage and does not damage the optical component or electronic component when peeled off. [Means for solving the problem]
[0008] The surface protective film according to an embodiment of the present invention comprises: A surface protection film including a pressure-sensitive adhesive layer, the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition, The pressure-sensitive adhesive composition comprises a base polymer, an ionic compound, and a fluorine-based compound, The surface free energy of the pressure-sensitive adhesive layer with respect to diiodomethane is 6 mJ / m 2 ~30mJ / m 2 It is.
[0009] In one embodiment, the content of the ionic compound is 0.2 parts by weight or more based on 100 parts by weight of the base polymer.
[0010] In one embodiment, the content of the fluorine-based compound is 0.05 part by weight or more based on 100 parts by weight of the base polymer.
[0011] In one embodiment, the base polymer is at least one selected from a polyol, a urethane prepolymer, an acrylic resin, a rubber resin, and a silicone resin.
[0012] In one embodiment, the pressure-sensitive adhesive layer contained in the surface protection film is attached to a glass plate and left to stand at a temperature of 23°C for 30 minutes, and then the surface protection film is peeled off from the glass plate at a temperature of 23°C at a peel angle of 180 degrees and a peel speed of 300 mm / min., and the peel force is 0.005 N / 25 mm to 0.1 N / 25 mm.
[0013] The optical member according to the embodiment of the present invention has the above-mentioned surface protection film attached thereto.
[0014] The electronic member according to the embodiment of the present invention has the above-mentioned surface protection film attached thereto. Effect of the Invention
[0015] According to the present invention, it is possible to provide a surface protection film including a pressure-sensitive adhesive layer that is attached to an exposed surface of an optical component or electronic component to prevent the surface of the optical component or electronic component from being scratched during processing, assembly, inspection, transportation, etc., typically in the manufacturing process of the optical component or electronic component, and that sufficiently suppresses peeling electrification voltage and does not damage the optical component or electronic component when peeled off. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] <<A. Surface protection film>> The surface protection film according to the embodiment of the present invention includes a pressure-sensitive adhesive layer.
[0018] The surface protection film may contain any other appropriate member as long as it contains a pressure-sensitive adhesive layer, as long as the effect of the present invention is not impaired. Typically, the surface protection film of the present invention contains a base layer and a pressure-sensitive adhesive layer.
[0019] Fig. 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. In Fig. 1, a surface protection film 10 includes a base layer 1 and a pressure-sensitive adhesive layer 2. In Fig. 1, the base layer 1 and the pressure-sensitive adhesive layer 2 are directly laminated together.
[0020] In Fig. 1, the surface of the pressure-sensitive adhesive layer 2 opposite to the base layer 1 may be provided with any appropriate release liner (sometimes called a release sheet or separator) for protection until use (not shown). Examples of release liners include release liners in which the surface of a base material (liner base material) such as paper or plastic film is treated with silicone, and release liners in which the surface of a base material (liner base material) such as paper or plastic film is laminated with a polyolefin resin.
[0021] Examples of plastic films usable as liner substrates include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.
[0022] The thickness of the release liner is preferably from 1 μm to 500 μm, more preferably from 3 μm to 450 μm, even more preferably from 5 μm to 400 μm, and particularly preferably from 10 μm to 300 μm.
[0023] The thickness of the surface protective film is preferably 5 μm to 500 μm, more preferably 10 μm to 450 μm, further preferably 15 μm to 400 μm, and particularly preferably 20 μm to 300 μm.
[0024] The adhesive layer contained in the surface protection film has a surface free energy of 6 mJ / m 2 ~30mJ / m 2 and more preferably 8 mJ / m 2 ~30mJ / m 2 and more preferably 10 mJ / m 2 ~30mJ / m 2 and particularly preferably 12 mJ / m 2 ~30mJ / m 2 If the surface free energy of the pressure-sensitive adhesive layer contained in the surface protection film with respect to diiodomethane is within the above range, it is possible to provide a surface protection film that sufficiently suppresses peeling electrification voltage and does not damage the adherend (typically, optical components or electronic components) when peeled off. If the surface free energy of the pressure-sensitive adhesive layer contained in the surface protection film with respect to diiodomethane is too low outside the above range, there is a risk that the peeling electrification voltage cannot be sufficiently suppressed. If the surface free energy of the pressure-sensitive adhesive layer contained in the surface protection film with respect to diiodomethane is too high outside the above range, there is a risk that the adherend will be contaminated.
[0025] In addition, the surface free energy of the pressure-sensitive adhesive layer contained in the surface protection film against diiodomethane can be easily measured as described below, and by designing the pressure-sensitive adhesive layer so that this surface free energy falls within the above-mentioned predetermined range, it is possible to provide a surface protection film that sufficiently suppresses peeling electrification voltage and does not damage the adherend (typically, optical components or electronic components) when peeled off. Here, the key points in designing the pressure-sensitive adhesive layer in the present invention are, typically, the use of an ionic compound and a fluorine-based compound in combination, and the selection of a fluorine compound. The selection of a fluorine compound can be, for example, by selecting a fluorine compound whose surface free energy falls within the above-mentioned predetermined range from among fluorine compounds in a specific category, and such a selection is a level of action that can be performed by a person skilled in the art without excessive trial and error.
[0026] The adhesive layer contained in the surface protection film has a peel strength of preferably 0.005N / 25mm to 0.1N / 25mm, more preferably 0.007N / 25mm to 0.08N / 25mm, even more preferably 0.01N / 25mm to 0.05N / 25mm, particularly preferably 0.01N / 25mm to 0.03N / 25mm, and most preferably 0.01N / 25mm to 0.02N / 25mm, when the surface protection film is attached to a glass plate, left at a temperature of 23°C for 30 minutes, and then peeled off from the glass plate at a peel angle of 180° and a peel speed of 300mm / min at a temperature of 23°C. If the peel strength is within the above range, it is difficult to peel off from the adherend, typically during the manufacturing process of an optical member or electronic member, and a surface protection film that is difficult to peel off after being attached to the exposed surface of the optical member or electronic member, and can be easily peeled off if peeling becomes necessary, can be provided.
[0027] The surface protection film can be produced by any suitable method. Examples of such a production method include (1) A method of applying a solution or a hot melt of a material for forming an adhesive layer onto a base layer, (2) A method of applying a solution or a hot melt of a material for forming an adhesive layer onto a separator to form an adhesive layer, and then transferring the adhesive layer onto a base layer; (3) A method of forming and coating a material for forming a pressure-sensitive adhesive layer on a base layer by extrusion; (4) A method of extruding a substrate layer and a pressure-sensitive adhesive layer in two or more layers, (5) A method of laminating a single layer of an adhesive layer on a substrate layer, or a method of laminating a double layer of an adhesive layer together with a laminate layer, (6) A method of laminating a pressure-sensitive adhesive layer and a base layer-forming material such as a film or a laminate layer in two or more layers, The above-mentioned manufacturing method can be used in accordance with any suitable manufacturing method.
[0028] Examples of the coating method that can be used include a roll coater method, a comma coater method, a die coater method, a reverse coater method, a silk screen method, and a gravure coater method.
[0029] The surface protection film according to an embodiment of the present invention is typically a surface protection film including an adhesive layer that is attached to the exposed surface of an optical component or electronic component to prevent the surface of the optical component or electronic component from being scratched during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical component or electronic component, and is a surface protection film that sufficiently suppresses peeling electrification voltage and does not damage the optical component or electronic component when peeled off.
[0030] The surface protective film according to the embodiment of the present invention has a glass peeling electrification voltage of preferably 3.0 kV or less, more preferably 2.5 kV or less, even more preferably 2.0 kV or less, particularly preferably 1.7 kV or less, and most preferably 1.5 kV or less. A method for measuring the glass peeling electrification voltage will be described later.
[0031] The surface protection film according to the embodiment of the present invention has an electrostatic potential at peeling off from an acrylic plate of preferably 4.0 kV or less, more preferably 3.5 kV or less, even more preferably 3.0 kV or less, still more preferably 2.5 kV or less, particularly preferably 2.0 kV or less, and most preferably 1.5 kV or less. A method for measuring the electrostatic potential at peeling off from an acrylic plate will be described later.
[0032] The surface protective film according to the embodiment of the present invention has a haze of preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, particularly preferably 2.8% or less, and most preferably 2.5% or less. If the haze of the surface protective film according to the embodiment of the present invention is within the above range, it is suitable as a surface protective film to be attached to the exposed surface of an optical component or an electronic component. In particular, if the haze of the surface protective film according to the embodiment of the present invention can be reduced to 3% or less, the inspectability of the surface protective film according to the embodiment of the present invention is further improved, which is more preferable. A method for measuring the haze will be described later.
[0033] The surface protection film according to the embodiment of the present invention has a residual adhesive strength to glass of preferably 70% or more, more preferably 80% or more, even more preferably 85% or more, particularly preferably 88% or more, and most preferably 90% or more. This residual adhesive strength to glass is an index of the extent to which the components of the adhesive layer of the surface protection film are transferred to the surface of the adherend and contaminate it. The higher the value of this residual adhesive strength to glass, the higher the risk of the surface protection film contaminating the adherend, and the lower the value of this residual adhesive strength to glass, the lower the risk of the surface protection film contaminating the adherend. A method for measuring this residual adhesive strength to glass will be described later.
[0034] <A-1. Adhesive layer> The pressure-sensitive adhesive layer is composed of a pressure-sensitive adhesive. The pressure-sensitive adhesive is formed from a pressure-sensitive adhesive composition. That is, the pressure-sensitive adhesive formed from the pressure-sensitive adhesive composition forms a layer shape to become the pressure-sensitive adhesive layer.
[0035] An adhesive can be defined as something formed from an adhesive composition. This is because an adhesive becomes an adhesive when an adhesive composition undergoes a crosslinking reaction due to heating or exposure to ultraviolet light, making it impossible and practical to directly identify an adhesive by its structure ("impossible / impractical circumstances"). Therefore, the definition of "something formed from an adhesive composition" appropriately identifies an adhesive as a "thing."
[0036] The adhesive layer can be formed by any suitable method. For example, the adhesive composition is applied to any suitable substrate, heated and dried as necessary, and cured as necessary to form an adhesive layer on the substrate. For example, the application method can be a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, air knife coater, spray coater, comma coater, direct coater, roll brush coater, etc.
[0037] The thickness of the pressure-sensitive adhesive layer is preferably 0.5 μm to 150 μm, more preferably 1 μm to 100 μm, even more preferably 2 μm to 80 μm, particularly preferably 3 μm to 50 μm, and most preferably 5 μm to 30 μm, in order to further exert the effects of the present invention.
[0038] The pressure-sensitive adhesive composition includes a base polymer, an ionic compound, and a fluorine-based compound. The pressure-sensitive adhesive composition includes a base polymer, an ionic compound, and a fluorine-based compound, and typically provides a surface protection film including a pressure-sensitive adhesive layer that is attached to an exposed surface of an optical member or an electronic member to prevent the surface of the optical member or the electronic member from being scratched during processing, assembly, inspection, transportation, or the like in the manufacturing process of the optical member or the electronic member, and that sufficiently suppresses peeling electrification voltage and does not damage the optical member or the electronic member when peeled off.
[0039] In the present invention, the effect of the present invention can be achieved by the pressure-sensitive adhesive composition containing both an ionic compound and a fluorine-based compound in addition to the base polymer. In particular, the effect of the present invention can be achieved remarkably by containing (using together) both an ionic compound and a fluorine-based compound according to a preferred embodiment described later (sometimes referred to as a "specific fluorine-based compound"). This is presumably because, by allowing an ionic compound capable of exhibiting an antistatic effect to coexist with a fluorine-based compound (preferably a specific fluorine-based compound) in the pressure-sensitive adhesive composition, the ionic compound becomes unevenly distributed on the surface side of the pressure-sensitive adhesive layer (the side to be bonded to the adherend) due to a synergistic effect with the fluorine-based compound (preferably a specific fluorine-based compound).
[0040] The content of the base polymer in the pressure-sensitive adhesive composition is preferably 60% by weight to 99.9% by weight, more preferably 65% by weight to 99.9% by weight, even more preferably 70% by weight to 99.9% by weight, particularly preferably 75% by weight to 99.9% by weight, and most preferably 80% by weight to 99.9% by weight, calculated as solid content. If the content of the base polymer in the pressure-sensitive adhesive composition is within the above range, calculated as solid content, a surface protection film can be provided that sufficiently suppresses peel electrification voltage and does not damage the adherend (typically, optical components or electronic components) when peeled off.
[0041] The content ratio of the ionic compound relative to 100 parts by weight of the base polymer is preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight to 5.0 parts by weight, even more preferably 0.5 parts by weight to 3.0 parts by weight, particularly preferably 0.7 parts by weight to 2.0 parts by weight, and most preferably 0.8 parts by weight to 1.5 parts by weight. If the content ratio of the ionic compound relative to 100 parts by weight of the base polymer is within the above range, it is possible to provide a surface protection film that sufficiently suppresses peeling electrification voltage and does not damage the adherend (typically optical components or electronic components) when peeled off. If the content ratio of the ionic compound relative to 100 parts by weight of the base polymer is too low outside the above range, the peeling electrification voltage may not be sufficiently suppressed. If the content ratio of the ionic compound relative to 100 parts by weight of the base polymer is too high outside the above range, the adherend may be contaminated.
[0042] The content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is preferably 0.05 parts by weight or more, more preferably 0.1 parts by weight to 5.0 parts by weight, even more preferably 0.15 parts by weight to 3.0 parts by weight, particularly preferably 0.2 parts by weight to 2.0 parts by weight, and most preferably 0.23 parts by weight to 1.5 parts by weight. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is within the above range, it is possible to provide a surface protection film that sufficiently suppresses peeling electrification voltage and does not damage the adherend (typically optical components or electronic components) when peeled off. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is too low outside the above range, the peeling electrification voltage may not be sufficiently suppressed. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is too high outside the above range, the adherend may be contaminated.
[0043] <A-1-1.ベースポリマー> The base polymer is preferably at least one selected from a urethane-based resin, an acrylic-based resin, a rubber-based resin, and a silicone-based resin. When the base polymer is at least one selected from a urethane-based resin, an acrylic-based resin, a rubber-based resin, and a silicone-based resin, it is possible to provide a surface protection film that more sufficiently suppresses the peeling electrification voltage and does not damage the adherend (typically, an optical member or an electronic member) when peeled off.
[0044] [A-1-1-1. Polyol] The polyol preferably reacts with a polyfunctional isocyanate compound to form a urethane resin. More specifically, the urethane resin is preferably formed from a composition containing a polyol and a polyfunctional isocyanate compound, and more specifically, the urethane resin is formed by curing the composition containing a polyol and a polyfunctional isocyanate compound. As a method for forming a urethane resin by curing a composition containing a polyol and a polyfunctional isocyanate compound, any appropriate method can be adopted within a range that does not impair the effects of the present invention, such as a urethane reaction method using bulk polymerization or solution polymerization.
[0045] The polyol may be of only one kind, or of two or more kinds.
[0046] The polyol is preferably at least one selected from polyester polyol, polyether polyol, polycaprolactone polyol, polycarbonate polyol, and castor oil polyol. In terms of being able to more effectively exhibit the effects of the present invention, the polyol is more preferably a polyether polyol.
[0047] The polyester polyol can be obtained, for example, by an esterification reaction between a polyol component and an acid component.
[0048] Examples of polyol components include ethylene glycol, diethylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 1,8-decanediol, octadecanediol, glycerin, trimethylolpropane, pentaerythritol, hexanetriol, and polypropylene glycol.
[0049] Examples of the acid component include succinic acid, methylsuccinic acid, adipic acid, pimelic acid, azelaic acid, sebacic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, dimer acid, 2-methyl-1,4-cyclohexanedicarboxylic acid, 2-ethyl-1,4-cyclohexanedicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, isophthalic acid, terephthalic acid, 1,4-naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and acid anhydrides thereof.
[0050] Examples of polyether polyols include polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide using water, low molecular weight polyols (propylene glycol, ethylene glycol, glycerin, trimethylolpropane, pentaerythritol, etc.), bisphenols (bisphenol A, etc.), dihydroxybenzenes (catechol, resorcin, hydroquinone, etc.) as initiators. Specific examples include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0051] Examples of polycaprolactone polyols include caprolactone-based polyester diols obtained by ring-opening polymerization of cyclic ester monomers such as ε-caprolactone and σ-valerolactone.
[0052] Examples of the polycarbonate polyol include polycarbonate polyols obtained by subjecting the above polyol components to a polycondensation reaction with phosgene; polycarbonate polyols obtained by subjecting the above polyol components to an ester exchange condensation reaction with carbonate diesters such as dimethyl carbonate, diethyl carbonate, dipropyl carbonate, diisopropyl carbonate, dibutyl carbonate, ethylbutyl carbonate, ethylene carbonate, propylene carbonate, diphenyl carbonate, and dibenzyl carbonate; copolymer polycarbonate polyols obtained by using two or more of the above polyol components in combination; polycarbonate polyols obtained by subjecting the above various polycarbonate polyols to an esterification reaction with a carboxyl group-containing compound; Examples of the polycarbonate polyol include polycarbonate polyols obtained by subjecting a recarbonate polyol to an etherification reaction with a hydroxyl group-containing compound; polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to an ester exchange reaction with an ester compound; polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to an ester exchange reaction with a hydroxyl group-containing compound; polyester-based polycarbonate polyols obtained by subjecting the above-mentioned various polycarbonate polyols to a polycondensation reaction with a dicarboxylic acid compound; and copolymerized polyether-based polycarbonate polyols obtained by copolymerizing the above-mentioned various polycarbonate polyols with an alkylene oxide.
[0053] Examples of castor oil-based polyols include castor oil-based polyols obtained by reacting castor oil fatty acid with the above-mentioned polyol component.Specific examples of castor oil-based polyols include castor oil-based polyols obtained by reacting castor oil fatty acid with polypropylene glycol.
[0054] The number average molecular weight Mn of the polyol is preferably 300 to 100000, more preferably 400 to 75000, further preferably 450 to 50000, and particularly preferably 500 to 30000. When the number average molecular weight Mn of the polyol is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically during the manufacturing process of an optical component or electronic component, and that is less likely to peel off after being attached to an exposed surface of the optical component or electronic component, and that can be more easily peeled off when peeling becomes necessary.
[0055] The polyol preferably contains a polyol (A1) having three OH groups and a number average molecular weight Mn of 300 to 100000. The polyol (A1) may be of only one kind, or of two or more kinds.
[0056] The content of polyol (A1) in the polyol is preferably 5% by weight or more, more preferably 25% by weight to 100% by weight, even more preferably 50% by weight to 100% by weight, particularly preferably 70% by weight to 100% by weight, and most preferably 90% by weight to 100% by weight. When the content of polyol (A1) in the polyol is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically during the manufacturing process of an optical or electronic component, and is less likely to peel off after being attached to an exposed surface of the optical or electronic component, and can be more easily peeled off if peeling becomes necessary.
[0057] The polyol (A1) preferably contains a polyol (A1a) having three OH groups and a number average molecular weight Mn of 8000 to 20000. The polyol (A1a) may be used alone or in combination of two or more kinds.
[0058] The content of polyol (A1a) in polyol (A1) is preferably 50% by weight or more, more preferably 60% by weight to 100% by weight, even more preferably 70% by weight to 95% by weight, particularly preferably 75% by weight to 93% by weight, and most preferably 80% by weight to 90% by weight. When the content of polyol (A1a) in polyol (A1) is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically during the manufacturing process of an optical or electronic component, and is less likely to peel off after being attached to an exposed surface of the optical or electronic component, and can be more easily peeled off if peeling becomes necessary.
[0059] The number average molecular weight Mn of the polyol (A1a) is 8000 to 20000, preferably 8000 to 18000, more preferably 8500 to 17000, even more preferably 9000 to 16000, particularly preferably 9500 to 15500, and most preferably 10000 to 15000. When the number average molecular weight Mn of the polyol (A1a) is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically during the manufacturing process of an optical component or electronic component, and is less likely to peel off after being attached to an exposed surface of the optical component or electronic component, and that can be more easily peeled off if peeling becomes necessary.
[0060] The polyol (A1) may contain a polyol (A1b) having three or more OH groups and a number average molecular weight Mn of not more than 5000. The polyol (A1b) may be one kind or two or more kinds.
[0061] The polyol (A1b) is preferably at least one selected from a polyol having three OH groups (triol), a polyol having four OH groups (tetraol), a polyol having five OH groups (pentaol), and a polyol having six OH groups (hexaol).
[0062] The content of polyol (A1b) in polyol (A1) is preferably 50% by weight or less, more preferably 0% by weight to 40% by weight, even more preferably 5% by weight to 30% by weight, particularly preferably 7% by weight to 25% by weight, and most preferably 10% by weight to 20% by weight. When the content of polyol (A1b) in polyol (A1) is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically during the manufacturing process of an optical or electronic component, after being attached to an exposed surface of the optical or electronic component, and that can be more easily peeled off if peeling becomes necessary.
[0063] The number average molecular weight Mn of the polyol (A1b) is preferably 500 to 5000, more preferably 600 to 4500, even more preferably 700 to 4000, particularly preferably 800 to 3500, and most preferably 900 to 3300. If the number average molecular weight Mn of the polyol (A1b) is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically, less likely to peel off after being attached to an exposed surface of an optical or electronic component during the manufacturing process of the optical or electronic component, and that can be more easily peeled off when peeling becomes necessary. If the number average molecular weight Mn of the polyol (A1b) is out of the above range, there is a particular concern that the adhesive strength increases with time, and excellent reworkability cannot be exhibited.
[0064] When the polyol (A1b) is at least one selected from a polyol having 4 OH groups (tetraol), a polyol having 5 OH groups (pentaol), and a polyol having 6 OH groups (hexaol), the total amount thereof, expressed as a content in the polyol (A1), is preferably 40% by weight or less, more preferably 0% by weight to 30% by weight, even more preferably 3% by weight to 20% by weight, particularly preferably 5% by weight to 15% by weight, and most preferably 7% by weight to 10% by weight. In the polyol (A1), when the polyol (A1b) is at least one selected from a polyol (tetraol) having four OH groups, a polyol (pentaol) having five OH groups, and a polyol (hexaol) having six OH groups, the total amount of the polyols is within the above range, and the surface protective film is less likely to peel off from the adherend, typically during the manufacturing process of an optical or electronic component, and is less likely to peel off after being attached to the exposed surface of the optical or electronic component, and can be more easily peeled off when peeling becomes necessary.Furthermore, the surface protective film has excellent transparency.
[0065] The content of at least one selected from polyol (tetraol) having four OH groups, polyol (pentaol) having five OH groups, and polyol (hexaol) having six OH groups in polyol (A1b) is preferably less than 10% by weight, more preferably 7% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 1% by weight or less, based on the total content of polyol (A1). If the content of at least one selected from polyol (tetraol) having four OH groups, polyol (pentaol) having five OH groups, and polyol (hexaol) having six OH groups in polyol (A1b) is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically in the manufacturing process of an optical component or electronic component, and is less likely to peel off after being attached to the exposed surface of the optical component or electronic component, and can be more easily peeled off if peeling becomes necessary. Furthermore, if the content of at least one selected from a polyol having four OH groups (tetraol), a polyol having five OH groups (pentaol), and a polyol having six OH groups (hexaol) in the polyol (A1b) falls outside the above range, the transparency of the surface protection film may decrease.
[0066] The polyol (A1) may contain a polyol (A1c) having 4 or more OH groups and a number average molecular weight Mn of 20000 or less. The polyol (A1c) may be one kind or two or more kinds.
[0067] The content of polyol (A1c) having 4 or more OH groups and a number average molecular weight Mn of 20000 or less in polyol (A1) is preferably less than 70% by weight, more preferably 60% by weight or less, even more preferably 50% by weight or less, particularly preferably 40% by weight or less, and most preferably 30% by weight or less. If the content of polyol (A1c) having 4 or more OH groups and a number average molecular weight Mn of 20000 or less in polyol (A1) is within the above range, it is possible to provide a surface protection film that is less likely to peel off from an adherend, typically during the manufacturing process of an optical or electronic component, after being attached to the exposed surface of the optical or electronic component, and that can be more easily peeled off when peeling is required. In addition, it is possible to provide a surface protection film with excellent transparency.
[0068] [A-1-1-2. Urethane prepolymer] The urethane prepolymer preferably reacts with a polyfunctional isocyanate compound to become a urethane resin. More specifically, the urethane resin is preferably formed from a composition containing a urethane prepolymer and a polyfunctional isocyanate compound, and more specifically, the urethane resin is formed by curing the composition containing a urethane prepolymer and a polyfunctional isocyanate compound. As a method for forming a urethane resin by curing a composition containing a polyol and a polyfunctional isocyanate compound, any appropriate manufacturing method can be adopted as long as it is a method for manufacturing a urethane resin using a so-called "urethane prepolymer" as a raw material.
[0069] In the description of the present invention, the "urethane prepolymer" is the "urethane prepolymer" that is generally referred to by those skilled in the art in the production of urethane resins, and is different from the "polyol" described in Section A-1-1-1.
[0070] The urethane prepolymer may be of only one type, or of two or more types.
[0071] The number average molecular weight Mn of the urethane prepolymer is preferably 3,000 to 1,000,000.
[0072] The urethane prepolymer is preferably a polyurethane polyol, and more preferably is obtained by reacting a polyester polyol (a1) or a polyether polyol (a2) alone or a mixture of (a1) and (a2) with a polyfunctional isocyanate compound in the presence or absence of a catalyst. The polyester polyol (a1) may be one type or two or more types. The polyether polyol (a2) may be one type or two or more types.
[0073] Any suitable polyester polyol can be used as the polyester polyol (a1). Examples of such polyester polyol (a1) include polyester polyols obtained by reacting an acid component with a glycol component. Examples of the acid component include terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, and trimellitic acid. Examples of the glycol component include ethylene glycol, propylene glycol, diethylene glycol, butylene glycol, 1,6-hexane glycol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, and butylethylpentanediol, and examples of the polyol component include glycerin, trimethylolpropane, and pentaerythritol. Other examples of the polyester polyol (a1) include polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerolactone) and polyvalerolactone.
[0074] The molecular weight of the polyester polyol (a1) can range from low to high. The molecular weight of the polyester polyol (a1) is preferably a number average molecular weight Mn of 100 to 100,000. If the number average molecular weight Mn is less than 100, the reactivity may be high and the polyurethane polyol may be easily gelled. If the number average molecular weight Mn is more than 100,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be low. The amount of the polyester polyol (a1) used is preferably 0 mol % to 90 mol % of the polyol constituting the polyurethane polyol.
[0075] Any suitable polyether polyol can be used as the polyether polyol (a2). Examples of such polyether polyol (a2) include polyether polyols obtained by polymerizing oxirane compounds such as ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran using low molecular weight polyols such as water, propylene glycol, ethylene glycol, glycerin, and trimethylolpropane as initiators. Specific examples of such polyether polyol (a2) include polyether polyols having two or more functional groups, such as polypropylene glycol, polyethylene glycol, and polytetramethylene glycol.
[0076] The molecular weight of the polyether polyol (a2) can range from low to high. The molecular weight of the polyether polyol (a2) is preferably a number average molecular weight Mn of 100 to 100,000. If the number average molecular weight Mn is less than 100, the reactivity may be high and the polyether polyol may be easily gelled. If the number average molecular weight Mn is more than 100,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be low. The amount of the polyether polyol (a2) used is preferably 0 mol % to 90 mol % of the polyol constituting the polyurethane polyol.
[0077] If necessary, the polyether polyol (a2) can be used in combination by replacing a part of it with glycols such as ethylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerin, trimethylolpropane, and pentaerythritol, or polyamines such as ethylenediamine, N-aminoethylethanolamine, isophoronediamine, and xylylenediamine.
[0078] As the polyether polyol (a2), only a bifunctional polyether polyol may be used, or a polyether polyol having a number average molecular weight Mn of 100 to 100,000 and at least three or more hydroxyl groups in one molecule may be used in part or in whole. When a polyether polyol having a number average molecular weight Mn of 100 to 100,000 and at least three or more hydroxyl groups in one molecule is used in part or in whole as the polyether polyol (a2), the balance between adhesive strength and removability can be improved. In such a polyether polyol, if the number average molecular weight Mn is less than 100, the reactivity may be high and the polyether polyol may be easily gelled. In addition, in such a polyether polyol, if the number average molecular weight Mn exceeds 100,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be reduced. The number average molecular weight Mn of such a polyether polyol is more preferably 100 to 10,000.
[0079] Any suitable catalyst may be used for obtaining the polyurethane polyol, such as, for example, a tertiary amine compound or an organometallic compound.
[0080] Examples of the tertiary amine compounds include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU).
[0081] Examples of organometallic compounds include tin-based compounds and non-tin-based compounds.
[0082] Examples of tin compounds include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and tin 2-ethylhexanoate.
[0083] Examples of non-tin compounds include titanium compounds such as dibutyltitanium dichloride, tetrabutyltitanium trichloride, and butoxytitanium trichloride; lead compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate; iron compounds such as iron 2-ethylhexanoate and iron acetylacetonate; cobalt compounds such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc compounds such as zinc naphthenate and zinc 2-ethylhexanoate; and zirconium compounds such as zirconium naphthenate.
[0084] When a catalyst is used to obtain polyurethane polyol, in a system in which two types of polyols, polyester polyol and polyether polyol, exist, problems such as gelation or clouding of the reaction solution are likely to occur in a system using a single catalyst due to the difference in reactivity. Therefore, by using two types of catalysts to obtain polyurethane polyol, it becomes easier to control the reaction rate, catalyst selectivity, etc., and these problems can be solved. Examples of such combinations of two types of catalysts include tertiary amine / organic metal system, tin system / non-tin system, and tin system / tin system, and preferably tin system / tin system, and more preferably a combination of dibutyltin dilaurate and tin 2-ethylhexanoate. The blending ratio of tin 2-ethylhexanoate / dibutyltin dilaurate is preferably less than 1, more preferably 0.2 to 0.6, by weight. If the blending ratio is 1 or more, gelation may occur easily due to the balance of catalytic activity.
[0085] When a catalyst is used in obtaining the polyurethane polyol, the amount of the catalyst used is preferably 0.01% by weight to 1.0% by weight based on the total amount of the polyester polyol (a1), the polyether polyol (a2), and the polyfunctional isocyanate compound.
[0086] When a catalyst is used in obtaining a polyurethane polyol, the reaction temperature is preferably less than 100° C., and more preferably 85° C. to 95° C. If the temperature is 100° C. or higher, it may become difficult to control the reaction rate and crosslinked structure, and it may become difficult to obtain a polyurethane polyol having a predetermined molecular weight.
[0087] When obtaining polyurethane polyol, it is not necessary to use a catalyst. In that case, the reaction temperature is preferably 100° C. or higher, more preferably 110° C. or higher. When obtaining polyurethane polyol without a catalyst, it is preferable to carry out the reaction for 3 hours or more.
[0088] Examples of methods for obtaining polyurethane polyol include 1) a method in which polyester polyol, polyether polyol, catalyst, and polyfunctional isocyanate compound are all charged into a flask, and 2) a method in which polyester polyol, polyether polyol, and catalyst are charged into a flask and polyfunctional isocyanate compound is added dropwise. As a method for obtaining polyurethane polyol, method 2) is preferred in terms of controlling the reaction.
[0089] When obtaining the polyurethane polyol, any suitable solvent may be used. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, acetone, etc. Among these solvents, toluene is preferred.
[0090] [A-1-1-3. Acrylic resin] As the acrylic resin, any appropriate acrylic resin may be adopted as long as the effects of the present invention are not impaired. The acrylic resin may be one type only, or two or more types.
[0091] The weight average molecular weight of the acrylic resin is preferably 300,000 to 2.5 million, more preferably 350,000 to 2 million, even more preferably 400,000 to 1.8 million, and particularly preferably 500,000 to 1.5 million, in order to further exert the effects of the present invention.
[0092] The acrylic resin is preferably an acrylic resin formed by polymerization from a composition (B) containing (component a) a (meth)acrylic acid alkyl ester in which the alkyl group in the alkyl ester moiety has 4 to 12 carbon atoms, and (component b) at least one selected from the group consisting of a (meth)acrylic acid ester having an OH group and (meth)acrylic acid, in order to more effectively exert the effects of the present invention. (Component a) and (component b) may each independently be one type or two or more types.
[0093] Examples of (meth)acrylic acid alkyl esters (component a) having an alkyl group of 4 to 12 carbon atoms in the alkyl ester moiety include n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, and dodecyl (meth)acrylate. Among these, in terms of being able to further exert the effects of the present invention, preferred are n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate, and more preferred are n-butyl acrylate and 2-ethylhexyl acrylate.
[0094] Examples of the at least one (b) selected from the group consisting of (meth)acrylic acid esters having an OH group and (meth)acrylic acid include (meth)acrylic acid esters having an OH group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, and (meth)acrylic acid. Among these, in terms of being able to more effectively exert the effects of the present invention, preferred are hydroxyethyl (meth)acrylate and (meth)acrylic acid, and more preferred are hydroxyethyl acrylate and acrylic acid.
[0095] The composition (B) may contain a copolymerizable monomer other than the components (a) and (b). The copolymerizable monomer may be one kind or two or more kinds.Examples of such copolymerizable monomers include carboxyl group-containing monomers (excluding (meth)acrylic acid) such as itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and acid anhydrides thereof (e.g., acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride); (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, N-methylol ... Amide group-containing monomers such as acrylamide; amino group-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; epoxy group-containing monomers such as glycidyl (meth)acrylate and methylglycidyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; N-vinyl-2-pyrrolidone, (meth)acryloylmorpholine, N-vinylpiperidone, N-vinylpiperazine, N-vinylpyrrole, and N-vinyl isopropyl alcohol. heterocyclic vinyl monomers such as midazole, vinylpyridine, vinylpyrimidine, and vinyloxazole; sulfonic acid group-containing monomers such as sodium vinyl sulfonate; phosphoric acid group-containing monomers such as 2-hydroxyethyl acryloyl phosphate; imide group-containing monomers such as cyclohexylmaleimide and isopropylmaleimide; isocyanate group-containing monomers such as 2-methacryloyloxyethyl isocyanate; (meth)acrylic acid esters having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, and isobornyl (meth)acrylate; (meth)acrylic acid esters having aromatic hydrocarbon groups such as phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, and benzyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyl toluene; olefins and dienes such as ethylene, butadiene, isoprene, and isobutylene; vinyl ethers such as vinyl alkyl ethers; and vinyl chloride.
[0096] As the copolymerizable monomer, a polyfunctional monomer may also be used. The polyfunctional monomer refers to a monomer having two or more ethylenically unsaturated groups in one molecule. As the ethylenically unsaturated group, any appropriate ethylenically unsaturated group may be used within a range that does not impair the effects of the present invention. Examples of such ethylenically unsaturated groups include radically polymerizable functional groups such as vinyl groups, propenyl groups, isopropenyl groups, vinyl ether groups (vinyloxy groups), and allyl ether groups (allyloxy groups). Examples of the polyfunctional monomer include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl(meth)acrylate, vinyl(meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, etc. Such polyfunctional monomers may be used alone or in combination of two or more kinds.
[0097] As the copolymerizable monomer, (meth)acrylic acid alkoxyalkyl esters may also be used. Examples of (meth)acrylic acid alkoxyalkyl esters include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate. The (meth)acrylic acid alkoxyalkyl esters may be one type or two or more types.
[0098] The content of the (meth)acrylic acid alkyl ester (component a) in which the alkyl group in the alkyl ester moiety has 4 to 12 carbon atoms is, in order to more effectively exert the effects of the present invention, preferably 30% by weight or more, more preferably 35% by weight to 99% by weight, even more preferably 40% by weight to 98% by weight, and particularly preferably 50% by weight to 95% by weight, relative to the total amount (100% by weight) of the monomer components constituting the acrylic polymer.
[0099] The content of at least one type (component b) selected from the group consisting of (meth)acrylic acid esters having an OH group and (meth)acrylic acid is preferably 1 wt % or more, more preferably 1 wt % to 30 wt %, even more preferably 2 wt % to 20 wt %, and particularly preferably 3 wt % to 10 wt %, relative to the total amount (100 wt %) of monomer components constituting the acrylic polymer, in order to further exert the effects of the present invention.
[0100] The composition (B) may contain any other appropriate components as long as the effects of the present invention are not impaired. Examples of such other components include a polymerization initiator, a chain transfer agent, and a solvent. The content of these other components may be any appropriate content as long as the effects of the present invention are not impaired.
[0101] The polymerization initiator may be a thermal polymerization initiator, a photopolymerization initiator (photoinitiator), etc., depending on the type of polymerization reaction. The polymerization initiator may be one type only, or two or more types.
[0102] The thermal polymerization initiator may be preferably used when obtaining an acrylic resin by solution polymerization. Examples of such thermal polymerization initiators include azo polymerization initiators, peroxide polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, etc.), and redox polymerization initiators. Among these thermal polymerization initiators, the azo polymerization initiators disclosed in JP-A-2002-69411 are particularly preferred. Such azo polymerization initiators are preferred in that decomposition products of the polymerization initiator are unlikely to remain in the acrylic resin as a portion that causes the generation of gas generated by heating (outgassing). Examples of azo polymerization initiators include 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as AIBN), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as AMBN), 2,2'-azobis(2-methylpropionate) dimethyl, and 4,4'-azobis-4-cyanovaleric acid.
[0103] The photopolymerization initiator can be preferably used when obtaining an acrylic polymer by active energy ray polymerization. Examples of the photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.
[0104] Examples of benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethan-1-one, and anisole methyl ether. Examples of acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin-based photopolymerization initiators include benzoin. Examples of benzyl-based photopolymerization initiators include benzyl. Examples of benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone. Examples of ketal-based photopolymerization initiators include benzyl dimethyl ketal. Examples of thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone.
[0105] In addition, when the base polymer is an acrylic resin, the adhesive composition may contain a crosslinking agent. By using the crosslinking agent, the cohesive strength of the adhesive can be improved, and the effect of the present invention can be more effectively exhibited. The crosslinking agent may be one type only, or two or more types.
[0106] Examples of the crosslinking agent include polyfunctional isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. Among these, at least one selected from the group consisting of polyfunctional isocyanate-based crosslinking agents and epoxy-based crosslinking agents is preferred in terms of further exerting the effects of the present invention.
[0107] Examples of polyfunctional isocyanate crosslinking agents include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of polyfunctional isocyanate crosslinking agents include commercially available products such as trimethylolpropane / tolylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), product name "Coronate HX" (Nippon Polyurethane Industry Co., Ltd.), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., product name "Takenate 110N").
[0108] Examples of epoxy crosslinking agents (polyfunctional epoxy compounds) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, and ethylene glycol diglycidyl ether. Examples of the epoxy crosslinking agent include diglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of the epoxy crosslinking agent include commercially available products such as "Tetrad C" (manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0109] The content of the crosslinking agent in the pressure-sensitive adhesive composition may be any appropriate content within the range that does not impair the effects of the present invention. For example, such a content is preferably 0.05 to 20 parts by weight, more preferably 0.1 to 18 parts by weight, even more preferably 0.5 to 15 parts by weight, and particularly preferably 0.5 to 10 parts by weight, relative to the solid content (100 parts by weight) of the acrylic resin, in terms of being able to further exhibit the effects of the present invention.
[0110] [A-1-1-4. Rubber-based resin] As the rubber-based resin, any suitable rubber-based resin used in a rubber-based adhesive, such as a known rubber-based adhesive described in JP-A-2015-074771, can be used within the scope of not impairing the effects of the present invention. These may be used alone or in combination of two or more kinds.
[0111] [A-1-1-5. Silicone-based resin] As the silicone-based resin, within the range that does not impair the effects of the present invention, for example, a silicone-based resin used in any appropriate silicone-based adhesive such as the silicone-based adhesive described in JP-A-2014-047280 can be adopted. These may be only one type or two or more types.
[0112] <A-1-2. Urethane-based resin>[ As described above, the polyol as the base polymer preferably reacts with a polyfunctional isocyanate compound to form a urethane-based resin. More specifically, preferably, a urethane-based resin is formed from a composition containing a polyol and a polyfunctional isocyanate compound. Specifically, a urethane-based resin is formed by curing a composition containing a polyol and a polyfunctional isocyanate compound. As a method for curing a composition containing a polyol and a polyfunctional isocyanate compound to form a urethane-based resin, any appropriate method can be adopted within the range that does not impair the effects of the present invention, such as a urethanization reaction method using bulk polymerization or solution polymerization.
[0113] Also, as described above, the urethane prepolymer as the base polymer preferably reacts with a polyfunctional isocyanate compound to form a urethane-based resin. More specifically, preferably, a urethane-based resin is formed from a composition containing a urethane prepolymer and a polyfunctional isocyanate compound. Specifically, a urethane-based resin is formed by curing a composition containing a urethane prepolymer and a polyfunctional isocyanate compound. As a method for curing a composition containing a urethane prepolymer and a polyfunctional isocyanate compound to form a urethane-based resin, any appropriate production method can be adopted as long as it is a method for producing a urethane-based resin using a so-called "urethane prepolymer" as a raw material.
[0114] That is, one preferred embodiment of the urethane-based resin is a urethane-based resin formed from a composition containing a polyol and a polyfunctional isocyanate compound. Another preferred embodiment of the urethane-based resin is a urethane-based resin formed from a composition containing a urethane prepolymer and a polyfunctional isocyanate compound.
[0115] [A-1-2-1. Urethane resin formed from a composition containing a polyol and a polyfunctional isocyanate compound]
[0116] The polyfunctional isocyanate compound may be of only one type, or of two or more types.
[0117] As the polyfunctional isocyanate compound, any suitable polyfunctional isocyanate compound that can be used in a urethane reaction can be used. Examples of such polyfunctional isocyanate compounds include polyfunctional aliphatic isocyanate compounds, polyfunctional alicyclic isocyanates, polyfunctional aromatic isocyanate compounds, and polyfunctional aromatic aliphatic isocyanate compounds.
[0118] Examples of polyfunctional aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, 2,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0119] Examples of polyfunctional alicyclic isocyanate compounds include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatemethyl)cyclohexane, 1,4-bis(isocyanatemethyl)cyclohexane, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0120] Examples of polyfunctional aromatic diisocyanate compounds include 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4',4"-triphenylmethane triisocyanate, dianisidine diisocyanate, and xylylene diisocyanate.
[0121] Examples of polyfunctional aromatic aliphatic isocyanate compounds include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.
[0122] Examples of the polyfunctional isocyanate compound include trimethylolpropane adducts of the various polyfunctional isocyanate compounds as described above, biuret compounds reacted with water, and trimers having an isocyanurate ring. These may also be used in combination.
[0123] The equivalent ratio of NCO group to OH group in the polyol and the polyfunctional isocyanate compound is preferably 5.0 or less, more preferably 0.1 to 3.0, even more preferably 0.2 to 2.5, even more preferably 0.3 to 2.5, even more preferably 0.3 to 2.0, particularly preferably 0.5 to 2.0, and most preferably 0.5 to 1.8. If the equivalent ratio of NCO group / OH group is within the above range, it is possible to provide a surface protection film that is not easily peeled off from an adherend, typically, during the manufacturing process of an optical member or an electronic member, is not easily peeled off after being attached to the exposed surface of the optical member or the electronic member, and can be easily peeled off when peeling becomes necessary. In addition, if the equivalent ratio of NCO group / OH group is within the above range, it is possible to reduce haze. In particular, if the haze can be reduced to 3% or less, the inspectability of the surface protection film according to the embodiment of the present invention is further improved.
[0124] The content ratio of the polyfunctional isocyanate compound is preferably 1.0% by weight to 30% by weight, more preferably 1.5% by weight to 27% by weight, even more preferably 2.0% by weight to 25% by weight, even more preferably 2.3% by weight to 23% by weight, even more preferably 2.3% by weight to 18% by weight, particularly preferably 2.5% by weight to 18% by weight, and most preferably 2.5% by weight to 16% by weight. If the content ratio of the polyfunctional isocyanate compound is within the above range, it is possible to provide a surface protection film that is not easily peeled off from an adherend, typically, during the manufacturing process of an optical member or an electronic member, is not easily peeled off after being attached to the exposed surface of the optical member or the electronic member, and can be easily peeled off when peeling becomes necessary. In addition, if the content ratio of the polyfunctional isocyanate compound is within the above range, it is possible to reduce haze. In particular, if the haze can be reduced to 3% or less, the inspectability of the surface protection film according to the embodiment of the present invention is further improved.
[0125] In order to cure the composition containing the polyol and the polyfunctional isocyanate compound, a catalyst is preferably used. Examples of such catalysts include organometallic compounds and tertiary amine compounds. The catalyst may be one type or two or more types.
[0126] Examples of the organometallic compound include iron-based compounds, tin-based compounds, titanium-based compounds, zirconium-based compounds, lead-based compounds, cobalt-based compounds, zinc-based compounds, etc. Among these, iron-based compounds and tin-based compounds are preferred in terms of reaction rate and pot life of the adhesive layer.
[0127] Examples of iron-based compounds include iron acetylacetonate and iron 2-ethylhexanoate.
[0128] Examples of tin compounds include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin maleate, dibutyltin dilaurate, dibutyltin diacetate, dibutyltin sulfide, tributyltin methoxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, dioctyltin dilaurate, tributyltin chloride, tributyltin trichloroacetate, and tin 2-ethylhexanoate.
[0129] Examples of titanium compounds include dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride.
[0130] Examples of the zirconium compound include zirconium naphthenate and zirconium acetylacetonate.
[0131] Examples of lead-based compounds include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate.
[0132] Examples of the cobalt-based compounds include cobalt 2-ethylhexanoate and cobalt benzoate.
[0133] Examples of zinc-based compounds include zinc naphthenate and zinc 2-ethylhexanoate.
[0134] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabic-(5,4,0)-undecene-7-ene.
[0135] The amount of the catalyst is preferably 0.005% by weight to 1.00% by weight, more preferably 0.01% by weight to 0.75% by weight, further preferably 0.01% by weight to 0.50% by weight, and particularly preferably 0.01% by weight to 0.20% by weight, relative to the polyol. If the amount of the catalyst is within the above range, it is possible to provide a surface protection film that is not easily peeled off from an adherend, typically, during the manufacturing process of an optical or electronic component, is not easily peeled off after being attached to the exposed surface of the optical or electronic component, and can be easily peeled off when peeling becomes necessary.
[0136] The composition containing the polyol and the polyfunctional isocyanate compound may contain any other appropriate components within the range that does not impair the effects of the present invention. Examples of such other components include antioxidants, ultraviolet absorbers, light stabilizers, resin components, tackifiers, crosslinking retarders, inorganic fillers, organic fillers, metal powders, pigments, foil-like materials, softeners, anti-aging agents, conductive agents, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, and solvents.
[0137] Among these other components, it is a preferred embodiment to include a deterioration inhibitor such as an antioxidant, an ultraviolet absorber, or a light stabilizer. By including an deterioration inhibitor in the pressure-sensitive adhesive composition, it is possible to obtain excellent adhesive residue prevention properties, such as the adhesive layer formed being less likely to leave an adhesive residue on the adherend even if it is stored in a heated state after being attached to the adherend. The deterioration inhibitor may be one type only, or two or more types. As the deterioration inhibitor, an antioxidant is particularly preferred.
[0138] Examples of the antioxidant include a radical chain inhibitor and a peroxide decomposer.
[0139] Examples of the radical chain inhibitor include phenol-based antioxidants and amine-based antioxidants.
[0140] Examples of the peroxide decomposer include sulfur-based antioxidants and phosphorus-based antioxidants.
[0141] Examples of the phenol-based antioxidant include monophenol-based antioxidants, bisphenol-based antioxidants, and polymeric phenol-based antioxidants.
[0142] Examples of monophenol-based antioxidants include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, and stearin-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate.
[0143] Examples of bisphenol-based antioxidants include 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4,4'-butylidenebis(3-methyl-6-t-butylphenol), and 3,9-bis[1,1-dimethyl-2-[β-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]ethyl]2,4,8,10-tetraoxaspiro[5,5]undecane.
[0144] Examples of polymeric phenolic antioxidants include 1,1,3-tris(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis-(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, 1,3,5-tris(3',5'-di-t-butyl-4'-hydroxybenzyl)-S-triazine-2,4,6-(1H,3H,5H)trione, and tocopherol.
[0145] Examples of the sulfur-based antioxidants include dilauryl 3,3'-thiodipropionate, dimyristyl 3,3'-thiodipropionate, and distearyl 3,3'-thiodipropionate.
[0146] Examples of the phosphorus-based antioxidant include triphenyl phosphite, diphenyl isodecyl phosphite, and phenyl diisodecyl phosphite.
[0147] Examples of the ultraviolet absorbing agent include benzophenone-based ultraviolet absorbing agents, benzotriazole-based ultraviolet absorbing agents, salicylic acid-based ultraviolet absorbing agents, anilide oxalate-based ultraviolet absorbing agents, cyanoacrylate-based ultraviolet absorbing agents, and triazine-based ultraviolet absorbing agents.
[0148] Examples of benzophenone-based ultraviolet absorbers include 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-dodecyloxybenzophenone, 2,2'-dihydroxy-4-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, and bis(2-methoxy-4-hydroxy-5-benzoylphenyl)methane.
[0149] Examples of the benzotriazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-4'-octoxyphenyl)benzotriazole, 2-[2'-hydroxy-3'-(3'',4'',5'',6'',-tetrahydrophthalimidomethyl)-5'-methylphenyl]benzotriazole, 2,2'methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], and 2-(2'-hydroxy-5'-methacryloxyphenyl)-2H-benzotriazole.
[0150] Examples of the salicylic acid-based ultraviolet absorbers include phenyl salicylate, p-tert-butylphenyl salicylate, and p-octylphenyl salicylate.
[0151] Examples of cyanoacrylate ultraviolet absorbers include 2-ethylhexyl-2-cyano-3,3'-diphenylacrylate, and ethyl-2-cyano-3,3'-diphenylacrylate.
[0152] Examples of the light stabilizer include hindered amine light stabilizers and ultraviolet light stabilizers.
[0153] Examples of the hindered amine light stabilizer include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and methyl-1,2,2,6,6-pentamethyl-4-piperidylsebacate.
[0154] Examples of ultraviolet stabilizers include nickel bis(octylphenyl)sulfide, [2,2'-thiobis(4-tert-octylphenolate)]-n-butylamine nickel, nickel complex-3,5-di-tert-butyl-4-hydroxybenzyl-phosphate monoethylate, nickel-dibutyldithiocarbamate, benzoate type quenchers, nickel-dibutyldithiocarbamate, and the like.
[0155] [A-1-2-2. Urethane resin formed from a composition containing a urethane prepolymer and a polyfunctional isocyanate compound] The polyfunctional isocyanate compound may be of only one type, or of two or more types.
[0156] As the polyfunctional isocyanate compound, any suitable polyfunctional isocyanate compound that can be used in the urethane reaction can be used. Examples of such polyfunctional isocyanate compounds include the "polyfunctional isocyanate compound" described in Section A-1-2.
[0157] The composition containing the urethane prepolymer and the polyfunctional isocyanate compound may contain any other appropriate components within the scope of not impairing the effects of the present invention. Examples of such other components include antioxidants, ultraviolet absorbers, light stabilizers, resin components, tackifiers, crosslinking retarders, inorganic fillers, organic fillers, metal powders, pigments, foil-like materials, softeners, anti-aging agents, conductive agents, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, and solvents.
[0158] Among these other components, it is a preferred embodiment to include a deterioration inhibitor such as an antioxidant, an ultraviolet absorber, or a light stabilizer. By including an deterioration inhibitor in the pressure-sensitive adhesive composition, it is possible to obtain excellent adhesive residue prevention properties, such as the adhesive layer formed being less likely to leave an adhesive residue on the adherend even when the adhesive layer is attached to the adherend and then stored in a heated state. The deterioration inhibitor may be one type only, or may be two or more types. As the deterioration inhibitor, an antioxidant is particularly preferred. For details of the antioxidant, the explanation in Section A-1-2-1 may be cited.
[0159] The equivalent ratio of NCO group to OH group in the urethane prepolymer and the polyfunctional isocyanate compound is preferably 5.0 or less, more preferably 0.01 to 3.0, even more preferably 0.02 to 2.0, even more preferably 0.03 to 2.0, even more preferably 0.03 to 1.9, particularly preferably 0.05 to 1.9, and most preferably 0.05 to 1.8. If the equivalent ratio of NCO group / OH group is within the above range, it is possible to provide a surface protection film that is not easily peeled off from an adherend, typically, during the manufacturing process of an optical member or an electronic member, is not easily peeled off after being attached to the exposed surface of the optical member or the electronic member, and can be easily peeled off when peeling becomes necessary. In addition, if the equivalent ratio of NCO group / OH group is within the above range, it is possible to reduce haze. In particular, if the haze can be reduced to 3% or less, the inspectability of the surface protection film according to the embodiment of the present invention is further improved.
[0160] The content ratio of the polyfunctional isocyanate compound is preferably 0.01% by weight to 30% by weight, more preferably 0.05% by weight to 25% by weight, still more preferably 0.1% by weight to 25% by weight, still more preferably 0.5% by weight to 25% by weight, still more preferably 0.5% by weight to 23% by weight, particularly preferably 1% by weight to 23% by weight, and most preferably 1% by weight to 21% by weight, based on the urethane prepolymer. When the content ratio of the polyfunctional isocyanate compound is within the above range, it is difficult to be easily peeled off from the adherend. Typically, during the manufacturing process of an optical member or an electronic member, peeling is less likely to occur after being attached to the exposed surface of the optical member or the electronic member, and when peeling is necessary, a surface protection film that can be easily peeled off can be provided. Further, when the content ratio of the polyfunctional isocyanate compound is within the above range, it is possible to reduce haze. In particular, if the haze can be reduced to 3% or less, the inspectability of the surface protection film according to the embodiment of the present invention is further improved.
[0161] <A-1-3. Ionic Compound> As the ionic compound, any suitable ionic compound can be adopted as long as the effects of the present invention are not impaired. Such an ionic compound is preferably an ionic liquid, and more preferably an ionic liquid containing a fluoro organic anion. By including both an ionic compound and a fluorine-based compound described later in addition to the base polymer in the pressure-sensitive adhesive composition, typically, in the manufacturing process of an optical member or an electronic member, for preventing damage to the surface of the optical member or the electronic member during processing, assembly, inspection, transportation, etc., a surface protection film including a pressure-sensitive adhesive layer that is adhered to the exposed surface of the optical member or the electronic member can be provided, which can sufficiently suppress the peeling charging voltage and does not damage the optical member or the electronic member during peeling.
[0162] The ionic compound may be only one kind or two or more kinds.
[0163] The ionic liquid means a molten salt (ionic compound) that is liquid at 25°C.
[0164] As the ionic liquid, any suitable ionic liquid may be adopted as long as it does not impair the effects of the present invention. As such an ionic liquid, preferably, it is an ionic liquid containing a fluoro organic anion, more preferably, it is an ionic liquid composed of a fluoro organic anion and an onium cation. By adopting an ionic liquid composed of a fluoro organic anion and an onium cation as the ionic liquid, and using it in combination with a fluorine-based compound described later, it is possible to provide a surface protective film including a pressure-sensitive adhesive layer that is attached to the exposed surface of an optical member or electronic member in order to prevent the surface of the optical member or electronic member from being scratched during processing, assembly, inspection, transportation, etc., in the manufacturing process of an optical member or electronic member, and that more sufficiently suppresses the peeling electrification voltage and does not damage the optical member or electronic member when peeled off.
[0165] As the onium cation that can constitute the ionic liquid, any suitable onium cation can be adopted within the scope that does not impair the effects of the present invention. As such an onium cation, preferably, at least one selected from a nitrogen-containing onium cation, a sulfur-containing onium cation, and a phosphorus-containing onium cation can be used. By selecting these onium cations and using them in combination with a fluorine-based compound described later, it is possible to provide a surface protection film that includes a pressure-sensitive adhesive layer and is attached to the exposed surface of an optical member or electronic member in order to prevent the surface of the optical member or electronic member from being scratched during processing, assembly, inspection, transportation, etc., in the manufacturing process of an optical member or electronic member, and that more sufficiently suppresses the peeling electrification voltage and does not damage the optical member or electronic member when peeled off.
[0166] The onium cation capable of forming the ionic liquid is preferably at least one selected from the cations having structures represented by the general formulas (1) to (5). [ka]
[0167] In general formula (1), Ra represents a hydrocarbon group having 4 to 20 carbon atoms and may contain a heteroatom, and Rb and Rc are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms and may contain a heteroatom, provided that when the nitrogen atom contains a double bond, Rc does not exist.
[0168] In general formula (2), Rd represents a hydrocarbon group having 2 to 20 carbon atoms and may contain a heteroatom, and Re, Rf, and Rg are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms and may contain a heteroatom.
[0169] In general formula (3), Rh represents a hydrocarbon group having 2 to 20 carbon atoms and may contain a heteroatom, and Ri, Rj, and Rk are the same or different and represent hydrogen or a hydrocarbon group having 1 to 16 carbon atoms and may contain a heteroatom.
[0170] In general formula (4), Z represents a nitrogen atom, a sulfur atom, or a phosphorus atom, and Rl, Rm, Rn, and Ro are the same or different and represent a hydrocarbon group having 1 to 20 carbon atoms, which may contain a heteroatom, provided that when Z is a sulfur atom, Ro does not exist.
[0171] In the general formula (5), X represents a Li atom, a Na atom, or a K atom.
[0172] Examples of the cation represented by the general formula (1) include a pyridinium cation, a pyrrolidinium cation, a piperidinium cation, a cation having a pyrroline skeleton, and a cation having a pyrrole skeleton.
[0173] Specific examples of the cation represented by the general formula (1) include pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-butyl-3,4-dimethylpyridinium cation, and 1,1-dimethylpyrrolidinium cation; 1-ethyl-1-methylpyrrolidinium cation, 1-methyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl-1-pentylpyrrolidinium cation, 1-ethyl-1-hexylpyrrolidinium cation, 1-ethyl-1-heptylpyrrolidinium cation pyrrolidinium cations such as 1,1-dipropylpyrrolidinium cation, 1-propyl-1-butylpyrrolidinium cation, and 1,1-dibutylpyrrolidinium cation; 1-propylpiperidinium cation, 1-pentylpiperidinium cation, 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, and 1-methyl-1- piperidinium cations such as heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, 1-propyl-1-butylpiperidinium cation, 1,1-dimethylpiperidinium cation, 1,1-dipropylpiperidinium cation, and 1,1-dibutylpiperidinium cation; 2-methyl-1-pyrroline cation;1-ethyl-2-phenylindole cation; 1,2-dimethylindole cation; 1-ethylcarbazole cation; and the like.
[0174] Among these, in terms of further exhibiting the effects of the present invention, preferred are pyridinium cations such as 1-ethylpyridinium cation, 1-butylpyridinium cation, 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-hexyl-3-methylpyridinium cation, 1-butyl-4-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation; 1-ethyl-1-methylpyrrolidinium cation, 1-methylpyridinium cation, and the like. 1-ethyl-1-propylpyrrolidinium cation, 1-methyl-1-butylpyrrolidinium cation, 1-methyl-1-pentylpyrrolidinium cation, 1-methyl-1-hexylpyrrolidinium cation, 1-methyl-1-heptylpyrrolidinium cation, 1-ethyl-1-propylpyrrolidinium cation, 1-ethyl-1-butylpyrrolidinium cation, 1-ethyl-1-pentylpyrrolidinium cation, 1-ethyl-1-hexylpyrrolidinium cation, 1-ethyl-1-heptylpyrrolidinium cation pyrrolidinium cations such as 1-methyl-1-ethylpiperidinium cation, 1-methyl-1-propylpiperidinium cation, 1-methyl-1-butylpiperidinium cation, 1-methyl-1-pentylpiperidinium cation, 1-methyl-1-hexylpiperidinium cation, 1-methyl-1-heptylpiperidinium cation, 1-ethyl-1-propylpiperidinium cation, 1-ethyl-1-butylpiperidinium cation, 1-ethyl-1-pent ...pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1-ethyl-1-pentylpiperidinium cation, 1- piperidinium cations such as 1-ethyl-1-hexylpiperidinium cation, 1-ethyl-1-heptylpiperidinium cation, 1-propyl-1-butylpiperidinium cation, etc., and more preferably, the 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, 1-octyl-4-methylpyridinium cation, 1-methyl-1-propylpyrrolidinium cation, and 1-methyl-1-propylpiperidinium cation.
[0175] Examples of the cation represented by the general formula (2) include an imidazolium cation, a tetrahydropyrimidinium cation, and a dihydropyrimidinium cation.
[0176] Specific examples of the cation represented by the general formula (2) include imidazolium cations such as 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, 1-tetradecyl-3-methylimidazolium cation, 1,2-dimethyl-3-propylimidazolium cation, 1-ethyl-2,3-dimethylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, and 1-hexyl-2,3-dimethylimidazolium cation; tetrahydropyrimidinium cations such as 1,2,3-trimethyl-1,4,5,6-tetrahydropyrimidinium cation, 1,2,3,4-tetramethyl-1,4,5,6-tetrahydropyrimidinium cation, and 1,2,3,5-tetramethyl-1,4,5,6-tetrahydropyrimidinium cation; dihydropyrimidinium cations such as 1,3-dimethyl-1,4-dihydropyrimidinium cation, 1,3-dimethyl-1,6-dihydropyrimidinium cation, 1,2,3-trimethyl-1,4-dihydropyrimidinium cation, 1,2,3-trimethyl-1,6-dihydropyrimidinium cation, 1,2,3,4-tetramethyl-1,4-dihydropyrimidinium cation, and 1,2,3,4-tetramethyl-1,6-dihydropyrimidinium cation; and the like.
[0177] Among these, from the viewpoint of further exerting the effects of the present invention, preferred are imidazolium cations such as the 1,3-dimethylimidazolium cation, 1,3-diethylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-decyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation and 1-tetradecyl-3-methylimidazolium cation, and more preferred are the 1-ethyl-3-methylimidazolium cation and 1-hexyl-3-methylimidazolium cation.
[0178] Examples of the cation represented by the general formula (3) include a pyrazolium cation and a pyrazolinium cation.
[0179] Specific examples of the cation represented by general formula (3) include pyrazolium cations such as 1-methylpyrazolium cation, 3-methylpyrazolium cation, 1-ethyl-2-methylpyrazolinium cation, 1-ethyl-2,3,5-trimethylpyrazolium cation, 1-propyl-2,3,5-trimethylpyrazolium cation, and 1-butyl-2,3,5-trimethylpyrazolium cation; and pyrazolinium cations such as 1-ethyl-2,3,5-trimethylpyrazolinium cation, 1-propyl-2,3,5-trimethylpyrazolinium cation, and 1-butyl-2,3,5-trimethylpyrazolinium cation.
[0180] Examples of the cation represented by general formula (4) include a tetraalkylammonium cation, a trialkylsulfonium cation, a tetraalkylphosphonium cation, and cations in which a part of the alkyl groups is substituted with an alkenyl group, an alkoxyl group, or an epoxy group.
[0181] Specific examples of the cation represented by the general formula (4) include tetramethylammonium cation, tetraethylammonium cation, tetrabutylammonium cation, tetrapentylammonium cation, tetrahexylammonium cation, tetraheptylammonium cation, triethylmethylammonium cation, tributylethylammonium cation, trimethylpropylammonium cation, trimethyldecylammonium cation, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation, glycidyltrimethylammonium cation, trimethylsulfonium cation, triethylsulfonium cation, tributylsulfonium cation, trihexylsulfonium cation, diethylmethylsulfonium cation, dibutylethylsulfonium cation, dimethyldecylsulfonium cation, tetramethylphosphonium cation, tetraethylphosphonium cation, tetrabutylphosphonium cation, tetrahexylphosphonium cation, tetraoctylphosphonium cation, triethylmethylphosphonium cation, tributylethylphosphonium cation, trimethyldecylphosphonium cation, and diallyldimethylammonium cation.
[0182] Among these, in terms of the ability to further exert the effects of the present invention, preferred are asymmetric tetraalkylammonium cations, trialkylsulfonium cations, and tetraalkylphosphonium cations such as triethylmethylammonium cation, tributylethylammonium cation, trimethyldecylammonium cation, diethylmethylsulfonium cation, dibutylethylsulfonium cation, dimethyldecylsulfonium cation, triethylmethylphosphonium cation, tributylethylphosphonium cation, and trimethyldecylphosphonium cation; N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium cation, glycidyltrimethylammonium cation, diallyldimethylammonium cation, N,N-dimethyl-N-ethyl-N-propylammonium cation, N,N-dimethyl-N-ethyl-N-butylammonium cation, N,N-dimethyl-N-ethyl-N-pentylammonium cation, and N,N-dimethyl-N-ethyl-N-hexylammonium cation; N,N-dimethyl-N-ethyl-N-heptyl ammonium cation, N,N-dimethyl-N-ethyl-N-nonyl ammonium cation, N,N-dimethyl-N,N-dipropyl ammonium cation, N,N-diethyl-N-propyl-N-butyl ammonium cation, N,N-dimethyl-N-propyl-N-pentyl ammonium cation, N,N-dimethyl-N-propyl-N-hexyl ammonium cation, N,N-dimethyl-N-propyl-N-heptyl ammonium cation, N,N-dimethyl-N -butyl-N-hexylammonium cation, N,N-diethyl-N-butyl-N-heptylammonium cation, N,N-dimethyl-N-pentyl-N-hexylammonium cation, N,N-dimethyl-N,N-dihexylammonium cation, trimethylheptylammonium cation, N,N-diethyl-N-methyl-N-propylammonium cation, N,N-diethyl-N-methyl-N-pentylammonium cation, N,N-diethyl-N-methyl-N-heptylammonium cation, N,Examples of the cation include N-diethyl-N-propyl-N-pentyl ammonium cation, triethylpropyl ammonium cation, triethylpentyl ammonium cation, triethylheptyl ammonium cation, N,N-dipropyl-N-methyl-N-ethyl ammonium cation, N,N-dipropyl-N-methyl-N-pentyl ammonium cation, N,N-dipropyl-N-butyl-N-hexyl ammonium cation, N,N-dipropyl-N,N-dihexyl ammonium cation, N,N-dibutyl-N-methyl-N-pentyl ammonium cation, N,N-dibutyl-N-methyl-N-hexyl ammonium cation, trioctylmethyl ammonium cation, and N-methyl-N-ethyl-N-propyl-N-pentyl ammonium cation, and more preferably the trimethylpropyl ammonium cation.
[0183] As the fluoro organic anion capable of constituting the ionic liquid, any appropriate fluoro organic anion can be adopted as long as it does not impair the effects of the present invention. Such a fluoro organic anion may be completely fluorinated (perfluorinated) or may be partially fluorinated.
[0184] Examples of such fluoro organic anions include fluorinated arylsulfonates, perfluoroalkanesulfonates, bis(fluorosulfonyl)imides, bis(perfluoroalkanesulfonyl)imides, cyanoperfluoroalkanesulfonylamides, bis(cyano)perfluoroalkanesulfonyl methides, cyano-bis-(perfluoroalkanesulfonyl)methides, tris(perfluoroalkanesulfonyl)methides, trifluoroacetates, perfluoroalkylates, tris(perfluoroalkanesulfonyl)methides, and (perfluoroalkanesulfonyl)trifluoroacetamides.
[0185] Among these fluoro organic anions, perfluoroalkylsulfonates, bis(fluorosulfonyl)imides, and bis(perfluoroalkanesulfonyl)imides are more preferred, and more specific examples include trifluoromethanesulfonate, pentafluoroethanesulfonate, heptafluoropropanesulfonate, nonafluorobutanesulfonate, bis(fluorosulfonyl)imide, and bis(trifluoromethanesulfonyl)imide.
[0186] Specific examples of the ionic liquid may be appropriately selected from the combinations of the above-mentioned cation components and the above-mentioned anion components. Specific examples of such ionic liquids include, for example, 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, and 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonate). 1-Butyl-3-methylpyridinium bis(pentafluoroethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1,1-dimethylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-ethylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide, 1-methyl-1 -butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-pentylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-hexylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-heptylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, fluoromethanesulfonyl)imide, 1-ethyl-1-pentylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-hexylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-heptylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1,1-dipropylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-propyl-1-butylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1,1-Dibutylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-pentylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dimethylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-ethylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(fluorosulfonyl)imide, 1-methyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-pentylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-hexylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-hexylpiperidinium bis(trifluoromethanesulfonyl)imide, butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-pentylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-hexylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-1-heptylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dipropylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-propyl-1-butylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dibutylpiperidinium bis(trifluoromethanesulfonyl)imide, 1,1-dimethylpyrrolidinium bis(pentafluoroethanesulfonyl)imide,1-Methyl-1-ethylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-butylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-pentylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-hexylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-heptylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-propylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-butylpyrrolidinium bis(pentafluoroethanesulfonyl)imide nyl)imide, 1-ethyl-1-pentylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-hexylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-heptylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dipropylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-propyl-1-butylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dibutylpyrrolidinium bis(pentafluoroethanesulfonyl)imide, 1-propylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-pentylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1,1-Dimethylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-ethylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-butylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-pentylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-hexylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-methyl-1-heptylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl 1-ethyl-1-propylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-butylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-pentylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-hexylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-1-heptylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1,1-dipropylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-propyl-1-butylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1,1-Dibutylpiperidinium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-3-methylimidazolium trifluoroacetate, 1-ethyl-3-methylimidazolium heptafluorobutyrate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-ethyl-3-methylimidazolium nonafluorobutanesulfonate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-3-methylimidazolium tris(trifluoromethanesulfonyl)methide, 1-butyl-3-methylimidazolium trifluoroacetate, 1-butyl-3-methylimidazolium heptafluorobutyrate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium perfluorobutanesulfonate, 1-butyl 1-Hexyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Hexyl-3-methylimidazolium trifluoromethanesulfonate, 1-Hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1,2-Dimethyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide, 1-Ethyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide, 1-Propyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide, 1- Butyl-2,3,5-trimethylpyrazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-2,3,5-trimethylpyrazolium bis(pentafluoroethanesulfonyl)imide, 1-propyl-2,3,5-trimethylpyrazolium bis(pentafluoroethanesulfonyl)imide, 1-butyl-2,3,5-trimethylpyrazolium bis(pentafluoroethanesulfonyl)imide, 1-ethyl-2,3,5-trimethylpyrazolium(trifluoromethanesulfonyl)trifluoroacetamide, 1-propyl-2,3,5-Trimethylpyrazolium(trifluoromethanesulfonyl)trifluoroacetamide, 1-butyl-2,3,5-trimethylpyrazolium(trifluoromethanesulfonyl)trifluoroacetamide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-propylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-butylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-pentyl Ammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl-N-nonylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N,N-dipropylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-butylammonium bis( trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-propyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-butyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-butyl-N-heptylammonium bis(trifluoromethanesulfonyl)imide fluoromethanesulfonyl)imide, N,N-dimethyl-N-pentyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N,N-dihexylammonium bis(trifluoromethanesulfonyl)imide, trimethylheptylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-propylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N,N-heptylammonium bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-propyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, triethylpropylammonium bis(trifluoromethanesulfonyl)imide, triethyl, n-butyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, n-butyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, n-butyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, n-butyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, n-butyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, n-butyl-N-methyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, n-butyl-N-methyl-N-hex ... trioctylmethylammonium bis(trifluoromethanesulfonyl)imide, n-methyl-N-ethyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, propyl-N-pentylammonium bis(trifluoromethanesulfonyl)imide, 1-butylpyridinium(trifluoromethanesulfonyl)trifluoroacetamide, 1-butyl-3-methylpyridinium(trifluoromethanesulfonyl)trifluoroacetamide, 1-ethyl-3-methylimidazolium(trifluoromethanesulfonyl)trifluoroacetamide, tetrahexylammonium bis(trifluoromethanesulfonyl)imide, diallyldimethylammonium trifluoromethanesulfonate, diallyldimethylammonium bis(trifluoromethanesulfonyl)imide, diallyldimethylammonium bis(pentafluoroethanesulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium trifluoromethanesulfonate, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide, N,Examples of the bis(pentafluoroethanesulfonyl)imide include N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(pentafluoroethanesulfonyl)imide, glycidyl trimethylammonium trifluoromethanesulfonate, glycidyl trimethylammonium bis(trifluoromethanesulfonyl)imide, glycidyl trimethylammonium bis(pentafluoroethanesulfonyl)imide, diallyl dimethyl ammonium bis(trifluoromethanesulfonyl)imide, diallyl dimethyl bis(pentafluoroethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
[0187] Among these ionic liquids, 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluoro ... fluorosulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium bis(fluorosulfonyl)imide.
[0188] Ionic liquids may be commercially available, but can also be synthesized as described below. The method for synthesizing ionic liquids is not particularly limited as long as the desired ionic liquid can be obtained, but generally, the halide method, hydroxide method, acid ester method, complex formation method, neutralization method, and the like are used, as described in the literature "Ionic Liquids - The Frontline and Future of Development" (published by CMC Publishing Co., Ltd.).
[0189] The synthesis methods for nitrogen-containing onium salts are described below for the halide method, hydroxide method, acid ester method, complex formation method, and neutralization method. However, other ionic liquids, such as sulfur-containing onium salts and phosphorus-containing onium salts, can also be obtained by similar methods.
[0190] The halide method is a method carried out by the reactions shown in reaction formulas (1) to (3). First, a tertiary amine is reacted with an alkyl halide to obtain a halide (reaction formula (1), chlorine, bromine, or iodine is used as the halogen).
[0191] The anion structure of the ionic liquid (A - ) with an acid (HA) or salt (MA, M is a cation that forms a salt with the desired anion, such as ammonium, lithium, sodium, or potassium) to obtain the desired ionic liquid (R 4 NA) is obtained.
[0192] [ka]
[0193] The hydroxide method is a method carried out by the reactions shown in reaction formulas (4) to (8). First, a halide (R 4 NX) is electrolyzed by ion exchange membrane electrolysis (reaction formula (4)), OH-type ion exchange resin method (reaction formula (5)) or silver oxide (Ag 2 O) (reaction equation (6)) produces a hydroxide (R 4 NOH) is obtained (chlorine, bromine, and iodine are used as halogens).
[0194] The obtained hydroxide is subjected to the reactions of reaction formulas (7) to (8) in the same manner as in the halogenation method described above to obtain the target ionic liquid (R 4 NA) is obtained.
[0195] [ka]
[0196] The acid ester method is a method carried out by the reactions shown in reaction formulas (9) to (11). First, a tertiary amine (R 3 N) is reacted with an acid ester to obtain an acid ester product (reaction formula (9). Examples of acid esters that can be used include esters of inorganic acids such as sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, and carbonic acid, and esters of organic acids such as methanesulfonic acid, methylphosphonic acid, and formic acid).
[0197] The acid ester thus obtained is subjected to the reactions of reaction formulas (10) to (11) in the same manner as in the halogenation method described above to obtain the desired ionic liquid (R 4 NA) can be obtained. Ionic liquids can also be obtained directly by using methyl trifluoromethanesulfonate, methyl trifluoroacetate, etc. as acid esters.
[0198] [ka]
[0199] The neutralization method is carried out by the reaction shown in reaction formula (12). 3 COOH,CF 3 SO 3 H,(CF 3 SO 2 ) 2 NH, (CF 3 SO 2 ) 3 CH, (C 2 F 5 SO 2 ) 2 It can be obtained by reacting with an organic acid such as NH.
[0200] [ka]
[0201] R described in the above reaction formulas (1) to (12) represents hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, and may contain a heteroatom.
[0202] <A-1-4. Fluorine-based compound> As the fluorine-based compound, any appropriate fluorine-based compound can be adopted as long as the effects of the present invention are not impaired. By including both a fluorine-based compound and the above-described ionic compound in addition to the base polymer, the pressure-sensitive adhesive composition typically provides a surface protection film including a pressure-sensitive adhesive layer that is adhered to the exposed surface of the optical member or the electronic member for preventing damage to the surface of the optical member or the electronic member during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical member or the electronic member, and can provide a surface protection film that sufficiently suppresses the peeling charging voltage and does not damage the optical member or the electronic member during peeling.
[0203] The fluorine-based compound may be only one kind or two or more kinds.
[0204] Examples of the fluorine-based compound include at least one selected from a fluorine-containing compound, a hydroxyl group-containing fluorine-based compound, and a crosslinkable functional group-containing fluorine-based compound.
[0205] Examples of the fluorine-containing compound include a compound having a fluoroaliphatic hydrocarbon skeleton, a fluorine-containing organic compound obtained by copolymerizing an organic compound and a fluorine-based compound, and a fluorine-containing compound containing an organic compound. Examples of the fluoroaliphatic hydrocarbon skeleton include fluoro C1-C10 alkanes such as fluoromethane, fluoroethane, fluoropropane, fluoroisopropane, fluorobutane, fluoroisobutane, fluorot-butane, fluoropentane, and fluorohexane.
[0206] A preferred embodiment of the fluorine-containing compound is an oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group ("specific fluorine-based compound"). By including (using in combination) both an ionic compound and the above-mentioned "specific fluorine-based compound", the effect of the present invention can be significantly exhibited. As described above, this is presumed to be because, by allowing an ionic compound capable of exhibiting an antistatic effect to coexist with a fluorine-based compound (preferably a specific fluorine-based compound) in the pressure-sensitive adhesive composition, the ionic compound becomes unevenly distributed on the surface side (the side to be bonded to the adherend) of the pressure-sensitive adhesive layer due to a synergistic effect with the fluorine-based compound (preferably a specific fluorine-based compound). Representative examples of the fluorine-containing group include fluorine-containing alkyl groups (e.g., CF 3 -, etc.) and / or fluorine-containing alkylene groups (e.g., -CF 2 -CF 2 -, etc. A hydrophilic group is a group having hydrophilicity, and hydrophilicity is translated into English as "hydrophilic" and is a property generally known to those skilled in the art as meaning "having affinity with water" (see, for example, McGraw-Hill Scientific and Technical Dictionary (Revised 3rd Edition, Nikkan Kogyo Shimbun, etc.)). A lipophilic group is a group having lipophilicity, and lipophilicity is translated into English as "lipophilic" and is a property generally known to those skilled in the art as meaning "having affinity with oil" (see, for example, McGraw-Hill Scientific and Technical Dictionary (Revised 3rd Edition, Nikkan Kogyo Shimbun, etc.).
[0207] The "specific fluorine-based compound" is more preferably an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, in that the effect of the present invention can be more effectively exhibited. If the "specific fluorine-based compound" does not contain a hydrophilic group or does not contain a lipophilic group, the effect of the present invention may not be fully exhibited.
[0208] A preferred embodiment of the fluorine-containing compound is a fluorine-containing compound having a surface tension of 26.0 mN / m to 27.0 mN / m when it is a 0.1% toluene solution, from the viewpoint of being able to more effectively exhibit the effects of the present invention (the surface tension of toluene is 27.9 mN / m). Thus, if the surface tension of the fluorine-containing compound when it is a 0.1% toluene solution is within a very narrow specific range of 26.0 mN / m to 27.0 mN / m, the effects of the present invention can be more effectively exhibited, and in particular, a remarkable and unexpected effect can be exhibited, in which both the peeling electrification voltage against glass and the peeling electrification voltage against resin can be sufficiently suppressed. In particular, when considering the intended use of the surface protection film in the preferred embodiment of the present invention, which is to be attached to the exposed surface of an optical member or electronic member, it is extremely important that the effect of both the peeling electrification voltage against glass and the peeling electrification voltage against resin can be sufficiently suppressed.
[0209] A particularly preferred embodiment of the fluorine-containing compound is an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and has a surface tension of 26.0 mN / m to 27.0 mN / m when it is dissolved in 0.1% toluene (the surface tension of toluene is 27.9 mN / m). A particularly preferred embodiment of the fluorine-containing compound is an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and has a surface tension of 26.0 mN / m to 27.0 mN / m when it is dissolved in 0.1% toluene (the surface tension of toluene is 27.9 mN / m), which can further exhibit the effects of the present invention, and in particular, can exhibit an extremely remarkable and unexpected effect that both the peeling electrification voltage against glass and the peeling electrification voltage against resin can be extremely sufficiently suppressed. In particular, when considering the intended use of the surface protection film in the preferred embodiment of the present invention, which is to be attached to the exposed surface of an optical member or electronic member, it is extremely important that the effect of both the peeling electrification voltage against glass and the peeling electrification voltage against resin can be extremely sufficiently suppressed.
[0210] As commercially available fluorine-containing compounds, for example, the following may be mentioned:
[0211] DIC Corporation's Megafuck series: Representative examples include "Megafac F-114", "Megafac F-251", "Megafac F-253", "Megafac F-281", "Megafac F-410", "Megafac F-430", "Megafac F-444", "Megafac F-477", "Megafac F-510", "Megafac F-551-A", "Megafac F-553", "Megafac F-554", "Megafac F-555-A", "Megafac F-556", "Megafac F-557", "Megafac F-558", "Megafac F-559", "Megafac F-560", and "Megafac F-561". , "Megafack F-562", "Megafack F-563", "Megafack F-565", "Megafack F-568", "Megafack F-569", "Megafack F-570", "Megafack F-576", "Megafack R-01", "Megafack R-40", "Megafack R-40-LM", "Megafack R-41", "Megafack R-41-LM", "Megafack R-94", "Megafack RS-56", "Megafack RS-72-K", "Megafack RS-75-A", "Megafack RS-75-NS", "Megafack RS-78", "Megafack RS-90", etc.
[0212] AGC Seimi Chemical's Surflon series: Representative examples include "S-242", "S-243", and "S-386".
[0213] Sumitomo 3M FC series: Representative examples include "FC-4430" and "FC-4432".
[0214] Neos Ftergent series: Representative examples include "Ftergent 100", "Ftergent 100C", "Ftergent 110", "Ftergent 150", "Ftergent 150CH", "Ftergent 250", and "Ftergent 400SW".
[0215] PF series manufactured by Kitamura Chemical Industry Co., Ltd.: Representative models include PF-136A, PF-156A, PF-151N, PF-636, PF-6320, PF-656, PF-6520, PF-651, PF-652, and PF-3320.
[0216] As the hydroxyl group-containing fluorine-based compound, for example, a conventionally known resin can be used, and examples thereof include hydroxyl group-containing fluorine resins described in WO 94 / 06870, JP 8 / 12921 A, JP 10 / 72569 A, JP 4 / 275379 A, WO 97 / 11130 A, and WO 96 / 26254 A. Other hydroxyl group-containing fluorine resins include fluoroolefin copolymers described in JP 8 / 231919 A, JP 10 / 265731 A, JP 10 / 204374 A, and JP 8 / 12922 A. Other examples include copolymers of compounds having fluorinated alkyl groups in hydroxyl group-containing compounds, fluorine-containing organic compounds in which fluorine-containing compounds are copolymerized in hydroxyl group-containing compounds, and fluorine-containing compounds containing hydroxyl group-containing organic compounds. Commercially available examples of such hydroxyl group-containing fluorine-based compounds include those sold under the trade name "Lumiflon" (manufactured by Asahi Glass Co., Ltd.), "Cefralcoat" (manufactured by Central Glass Co., Ltd.), "Zaflon" (manufactured by Toa Gosei Co., Ltd.), and "Zeffle" (manufactured by Daikin Industries, Ltd.).
[0217] Examples of the crosslinkable functional group-containing fluorine-based compound include carboxylic acid compounds having a fluorinated alkyl group such as perfluorooctanoic acid, copolymers of compounds having a fluorinated alkyl group and a crosslinkable functional group-containing compound, fluorine-containing organic compounds obtained by copolymerizing a crosslinkable functional group-containing compound with a fluorine-containing compound, and fluorine-containing compounds containing a crosslinkable functional group-containing compound. Commercially available examples of such crosslinkable functional group-containing fluorine-based compounds include those under the trade names "Megafac F-570", "Megafac RS-55", "Megafac RS-56", "Megafac RS-72-K", "Megafac RS-75", "Megafac RS-76-E", "Megafac RS-76-NS", "Megafac RS-78", and "Megafac RS-90" (manufactured by DIC Corporation).
[0218] Among commercially available fluorine-containing compounds, a representative example of the above-mentioned "oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group" is the following product manufactured by DIC Corporation: "Megafac F-477" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.4 mN / m), "Megafac F-551-A" (oligomer containing fluorine-containing groups and lipophilic groups, surface tension when dissolved in 0.1% toluene = 25.6 mN / m), "Megafac F-553" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups; surface tension when dissolved in 0.1% toluene = 26.4 mN / m), "Megafac F-554" (fluorine-containing / lipophilic group-containing oligomer, surface tension when dissolved in 0.1% toluene = 25.0 mN / m), "Megafac F-555-A" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 20.4 mN / m), "Megafac F-557" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.3 mN / m), "Megafac F-559" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension = 26.1 mN / m when made into a 0.1% toluene solution), "Megafac F-563" (an oligomer containing a fluorine-containing group and a lipophilic group, surface tension = 20.2 mN / m when made into a 0.1% toluene solution), "Megafac F-569" (an oligomer containing a fluorine-containing group and a hydrophilic group, surface tension = 19.7 mN / m when made into a 0.1% toluene solution), and the like.
[0219] Among the fluorine-containing compounds available as commercial products, typical examples of those corresponding to the aforementioned "oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and having a surface tension of 26.0 mN / m to 27.0 mN / m when made into a 0.1% toluene solution (the surface tension of toluene is 27.9 mN / m), fluorine-containing compound" are those manufactured by DIC Corporation, "Megafac F-477" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension = 26.4 mN / m when made into a 0.1% toluene solution), "Megafac F-553" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension = 26.4 mN / m when made into a 0.1% toluene solution), "Megafac F-557" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension = 26.3 mN / m when made into a 0.1% toluene solution), "Megafac F-559" (an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, surface tension = 26.1 mN / m when made into a 0.1% toluene solution), and the like.
[0220] <A-1-5. Other Components> The pressure-sensitive adhesive composition may contain any other suitable components within the scope that does not impair the effect of the present invention.Such other components include, for example, resin components, crosslinking accelerators, crosslinking catalysts, silane coupling agents, silicone additives such as modified silicone oils, tackifier resins (rosin derivatives, polyterpene resins, petroleum resins, oil-soluble phenols, etc.), antiaging agents, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), foil-like materials, ultraviolet absorbers, antioxidants, light stabilizers, chain transfer agents, plasticizers, softeners, conductive agents, stabilizers, surface lubricants, corrosion inhibitors, heat stabilizers, polymerization inhibitors, lubricants, solvents, catalysts, etc.
[0221] The pressure-sensitive adhesive composition may contain, as another component, typically, modified silicone oil, within a range that does not impair the effects of the present invention. When the pressure-sensitive adhesive composition contains modified silicone oil, the effect of antistatic properties can be exhibited. In particular, when used in combination with an ionic liquid, the effect of antistatic properties can be exhibited more effectively.
[0222] When the pressure-sensitive adhesive composition contains modified silicone oil, the content is preferably 0.001 to 50 parts by weight, more preferably 0.005 to 40 parts by weight, even more preferably 0.007 to 30 parts by weight, particularly preferably 0.008 to 20 parts by weight, and most preferably 0.01 to 10 parts by weight, relative to 100 parts by weight of the base polymer. By adjusting the content of the modified silicone oil within the above range, the antistatic effect can be more effectively exhibited.
[0223] As the modified silicone oil, any suitable modified silicone oil can be used as long as it does not impair the effects of the present invention. Examples of such modified silicone oils include modified silicone oils available from Shin-Etsu Chemical Co., Ltd.
[0224] The modified silicone oil is preferably a polyether modified silicone oil, which can more effectively exhibit the antistatic properties.
[0225] Examples of polyether-modified silicone oils include side-chain type polyether-modified silicone oils, both-end type polyether-modified silicone oils, etc. Among these, both-end type polyether-modified silicone oils are preferred because they can fully and more effectively exhibit the antistatic properties.
[0226] ≪A-2. Base material layer≫ The base material layer may be a single layer or may be two or more layers. The base material layer may be a stretched layer.
[0227] The thickness of the base layer is preferably 4 μm to 450 μm, more preferably 8 μm to 400 μm, further preferably 12 μm to 350 μm, and particularly preferably 16 μm to 250 μm.
[0228] For the surface of the base layer on which the pressure-sensitive adhesive layer is not applied, a release treatment may be performed by adding, for example, a fatty acid amide, polyethyleneimine, a long-chain alkyl additive, or the like to the base layer in order to form a roll that is easy to unwind, or a coating layer made of any suitable release agent such as a silicone-based, long-chain alkyl-based, or fluorine-based release agent may be provided.
[0229] The material of the substrate layer may be any suitable material depending on the application. Examples include plastic, paper, metal film, nonwoven fabric, etc. Plastic is preferable. That is, the substrate layer is preferably a plastic film. The substrate layer may be made of one material or two or more materials. For example, it may be made of two or more plastics.
[0230] Examples of the plastics include polyester resins, polyamide resins, and polyolefin resins. Examples of the polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resins include homopolymers of olefin monomers and copolymers of olefin monomers. Specific examples of the polyolefin resins include homopolypropylene; propylene copolymers such as block, random, and graft copolymers with an ethylene component as a copolymerization component; reactor TPO; ethylene polymers such as low density, high density, linear low density, and ultra-low density; ethylene copolymers such as ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, ethylene-methacrylic acid copolymers, and ethylene-methyl methacrylate copolymers; and the like.
[0231] The substrate layer may contain any suitable additive as necessary. Examples of additives that may be contained in the substrate layer include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, and pigments. The type, number, and amount of additives that may be contained in the substrate layer may be appropriately set according to the purpose. In particular, when the material of the substrate layer is plastic, it is preferable to contain some of the above additives for the purpose of preventing deterioration, etc. From the viewpoint of improving weather resistance, etc., particularly preferred additives include antioxidants, ultraviolet absorbers, light stabilizers, and fillers.
[0232] Any suitable antioxidant may be used as the antioxidant. Examples of such antioxidants include phenol-based antioxidants, phosphorus-based processing heat stabilizers, lactone-based processing heat stabilizers, sulfur-based heat stabilizers, and phenol-phosphorus-based antioxidants. The content of the antioxidant is preferably 1% by weight or less, more preferably 0.5% by weight or less, and even more preferably 0.01% by weight to 0.2% by weight, based on the base resin of the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0233] Any suitable ultraviolet absorbing agent may be used as the ultraviolet absorbing agent. Examples of such ultraviolet absorbing agents include benzotriazole-based ultraviolet absorbing agents, triazine-based ultraviolet absorbing agents, and benzophenone-based ultraviolet absorbing agents. The content of the ultraviolet absorbing agent is preferably 2% by weight or less, more preferably 1% by weight or less, and even more preferably 0.01% by weight to 0.5% by weight, based on the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0234] Any suitable light stabilizer may be used as the light stabilizer. Examples of such light stabilizers include hindered amine light stabilizers and benzoate light stabilizers. The content of the light stabilizer is preferably 2% by weight or less, more preferably 1% by weight or less, and even more preferably 0.01% by weight to 0.5% by weight, based on the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0235] Any suitable filler may be used as the filler. Examples of such fillers include inorganic fillers. Specific examples of inorganic fillers include carbon black, titanium oxide, and zinc oxide. The content of the filler is preferably 20% by weight or less, more preferably 10% by weight or less, and even more preferably 0.01% by weight to 10% by weight, based on the base resin forming the substrate layer (when the substrate layer is a blend, the blend is the base resin).
[0236] Further, as additives, for the purpose of imparting antistatic properties, preferred examples include inorganic, low-molecular-weight and high-molecular-weight antistatic agents such as surfactants, inorganic salts, polyhydric alcohols, metal compounds, and carbon. In particular, high-molecular-weight antistatic agents and carbon are preferred from the viewpoints of preventing contamination and maintaining adhesion.
[0237] ≪≪B.Applications≫≫ The surface protective film according to the embodiment of the present invention is typically a surface protective film including a pressure-sensitive adhesive layer that is attached to an exposed surface of an optical member or electronic member in order to prevent the surface of the optical member or electronic member from being scratched during processing, assembly, inspection, transportation, etc., in the manufacturing process of the optical member or electronic member, and can exhibit the effect of sufficiently suppressing peeling electrification voltage and not damaging the optical member or electronic member when peeled. Therefore, it can be suitably used for surface protection of optical members and electronic members. The optical member of the present invention is one to which the surface protective film of the present invention is attached. The electronic member of the present invention is one to which the surface protective film of the present invention is attached. EXAMPLES
[0238] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The test and evaluation methods in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.
[0239] <Measurement of surface free energy of adhesive layer surface against diiodomethane> The surface protection film from which the separator had been removed was cut to a size of 50 mm wide and 100 mm long, and the adhesive layer surface was placed on top and fixed to a contact angle meter (Kyowa Interface Science Co., Ltd., model "CA-X"), and 2.0 μL of water was dropped onto the adhesive layer surface to measure the contact angle. Next, 2.0 μL of diiodomethane was dropped in the same manner to measure the contact angle. The surface free energy of the adhesive layer surface with respect to diiodomethane was calculated using the Owens-Wendt method from the contact angle values of the above two liquids.
[0240] <Measurement of peel strength from glass plate (after leaving at 23℃ for 30 minutes)> The adhesive layer side of the surface protection film (25 mm wide x 140 mm long) from which the separator had been removed was attached to a glass plate (soda-lime glass, manufactured by Matsunami Glass Industry Co., Ltd.) using a 2 kg hand roller back and forth once, and left at an environmental temperature of 23°C for 30 minutes. The evaluation sample obtained as described above was measured with a tensile tester. Shimadzu Corporation's product name "Autograph AG-Xplus HS 6000mm / min high speed model (AG-50NX plus)" was used as the tensile tester. The evaluation sample was set in the tensile tester, and the tensile test was started. Specifically, the load when the surface protection film was peeled off from the glass plate was measured, and the average load at that time was taken as the peel force of the surface protection film from the glass plate. The conditions of the tensile test were a test environment temperature of 23°C, a peel angle of 180°, and a peel speed (tensile speed) of 300mm / min.
[0241] <Measurement of glass peeling withstand voltage and acrylic board peeling electrification voltage> The surface protection film from which the separator had been removed was cut to a size of 70 mm in width and 100 mm in length, and was pressed onto the surface of glass (soda lime glass, manufactured by Matsunami Glass Industry Co., Ltd.) or an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a hand roller so that one end of the surface protection film protruded 30 mm beyond the edge of the glass. The sample was left for one day in an environment of 23°C x 50% RH, and then set at a predetermined position on a sample fixing table with a height of 20 mm. The end of the surface protection film protruding 30 mm from the glass was fixed to an automatic winding machine, and peeled off at a peeling angle of 150° and a peeling speed of 30 m / min. The electric potential of the adherend surface generated at this time was measured by a potential meter (manufactured by Shishido Electrostatics, model "STATIRON DZ-4") fixed at a position 30 mm high from the center of the adherend, and was taken as the peeling electrification voltage to glass or the peeling electrification voltage to acrylic plate. The measurement was performed in an environment of 23°C and 50% RH.
[0242] <Measurement of remaining adhesive strength to glass> A surface protection film was applied to the entire surface of a glass plate (Matsunami Glass, 1.35 mm x 10 cm x 10 cm) using a hand roller, and after storing for 24 hours in an atmosphere of 23°C temperature and 55% RH humidity, the surface protection film was peeled off at a speed of 0.3 m / min, and a 19 mm wide No. 31B tape (Nitto Denko Corporation, substrate thickness: 25 μm) cut to a length of 150 mm was applied with one reciprocation of a 2.0 kg roller in an atmosphere of 23°C temperature and 55% RH humidity. After curing for 30 minutes in an atmosphere of 23°C temperature and 55% RH, a tensile tester (Shimadzu Corporation, product name "Autograph AG-Xplus HS 6000 mm / min high speed model (AG-50NX plus)") was used to measure the adhesive strength by peeling at a peel angle of 180 degrees and a pulling speed of 300 mm / min. Separately, the adhesive strength of a 19 mm wide No. 31B tape was measured on a glass plate that had not been treated as described above, and the residual adhesion rate was calculated using the following formula. Residual adhesion rate (%) = (Adhesive strength of No. 31B to glass plate after peeling off surface protective film / Adhesive strength of No. 31B to glass plate) x 100 This residual adhesion rate to glass is an index of the degree to which the adhesive component of the surface protection film is transferred to the surface of the adherend and contaminates the adherend. The higher the value of this residual adhesion rate to glass, the more likely the surface protection film is to contaminate the adherend, and the lower the value of this residual adhesion rate to glass, the less likely the surface protection film is to contaminate the adherend.
[0243] <Haze measurement> The adhesive solution obtained in the following Examples and Comparative Examples was applied to the release-treated surface of a 75 μm-thick polyester film (trade name: Diafoil MRF75, manufactured by Mitsubishi Chemical Corporation) with one side treated for release with silicone, and dried under the conditions described in the following Examples and Comparative Examples to prepare an adhesive layer. Next, the surface of the adhesive layer was covered with a 75 μm-thick polyester film (trade name: Diafoil MRE75, manufactured by Mitsubishi Chemical Corporation) with one side treated for release with silicone, with the release-treated surface of the film facing the adhesive layer, and aged at room temperature for 5 days. Two pieces of 50 mm x 50 mm thick cardboard with a 20 mm x 20 mm hole in the center were prepared, and a sample was attached to one of them by rolling it back and forth with a hand roller, and then the other was attached. The evaluation samples obtained as described above were measured with "HM-150N" manufactured by Murakami Color Research Laboratory.
[0244] <Explanation of fluorine-containing compounds used in the examples and comparative examples> The fluorine-containing compounds used in the examples and comparative examples are as follows. "Megafac F-477" (DIC Corporation, fluorine-containing, hydrophilic and lipophilic oligomer, surface tension of 0.1% toluene solution = 26.4mN / m), "Megafac F-551-A" (DIC Corporation, fluorine-containing and lipophilic group-containing oligomer, surface tension when dissolved in 0.1% toluene = 25.6 mN / m), "Megafac F-553" (DIC Corporation, fluorine-containing, hydrophilic and lipophilic oligomer, surface tension of 0.1% toluene solution = 26.4mN / m), "Megafac F-554" (DIC Corporation, fluorine-containing and lipophilic group-containing oligomer, surface tension when dissolved in 0.1% toluene = 25.0 mN / m), "Megafac F-555-A" (DIC Corporation, fluorine-containing, hydrophilic and lipophilic oligomer, surface tension of 0.1% toluene solution = 20.4mN / m), "Megafac F-557" (DIC Corporation, fluorine-containing, hydrophilic and lipophilic oligomer, surface tension of 0.1% toluene solution = 26.3mN / m), "Megafac F-559" (DIC Corporation, fluorine-containing, hydrophilic and lipophilic oligomer, surface tension of 0.1% toluene solution = 26.1mN / m), "Megafac F-563" (DIC Corporation, fluorine-containing and lipophilic group-containing oligomer, surface tension when dissolved in 0.1% toluene = 20.2 mN / m), "Megafac F-569" (DIC Corporation, fluorine-containing and hydrophilic group-containing oligomer, surface tension when dissolved in 0.1% toluene = 19.7 mN / m),
[0245] Example 1 As polyols, 85 parts by weight of Preminol S3011 (manufactured by Asahi Glass Co., Ltd., Mn=10000) which is a polyol having three hydroxyl groups, 13 parts by weight of Sannix GP3000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=3000) which is a polyol having three hydroxyl groups, 2 parts by weight of Sannix GP1000 (manufactured by Sanyo Chemical Industries, Ltd., Mn=1000) which is a polyol having three hydroxyl groups, 18 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, and Nursem ferric as a catalyst. (manufactured by Nippon Chemical Industry Co., Ltd.), 0.02 parts by weight of Megafac F-553 (manufactured by DIC Corporation) of a fluorine-based oligomer, 1 part by weight of 1-ethyl-3-methylimidazolium tri(fluoromethanesulfonyl)imide (AS110, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an ionic compound, and 1 part by weight of 1-ethyl-3-methylimidazolium tri(fluoromethanesulfonyl)imide as an ionic compound were diluted with ethyl acetate to a total solid content of 35% by weight to obtain a urethane-based adhesive solution. The urethane-based adhesive solution was then applied to a substrate made of polyester resin (trade name "T100-75S", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) so that the thickness after drying was 20 μm, and the solution was cured and dried under conditions of a drying temperature of 130° C. and a drying time of 2 minutes. Next, the silicone-treated surface of a release sheet (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin with a thickness of 25 μm and one side of which was silicone-treated was attached to the surface of the obtained adhesive layer to obtain a surface protection film (1). The samples were aged at room temperature for 5 days and then evaluated. The release sheet was peeled off immediately before the evaluation. The results are shown in Table 1.
[0246] Example 2 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (2) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-569", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protective film (2). The results are shown in Table 1.
[0247] Example 3 As shown in Table 1, except that the amount of the fluorine-based oligomer (product name "F-554", manufactured by DIC) was changed to 1 part by weight in terms of solid content, an adhesive layer made of the adhesive composition (3) was produced in the same manner as in Example 1, and a surface protective film (3) was obtained. The results are shown in Table 1.
[0248] Example 4 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (4) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (4). The results are shown in Table 1.
[0249] Example 5 As shown in Table 1, the same procedure as in Example 1 was carried out except that the amount of the fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the amount of the ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.5 parts by weight, to obtain a surface protection film (5). The results are shown in Table 1.
[0250] Example 6 As shown in Table 1, the same procedure as in Example 1 was carried out except that the amount of the fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the amount of the ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.25 parts by weight. An adhesive layer made of the adhesive composition (6) was produced, and a surface protection film (6) was obtained. The results are shown in Table 1.
[0251] Example 7 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (7) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-555-A", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (7). The results are shown in Table 1.
[0252] Example 8 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (8) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-559", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (8). The results are shown in Table 1.
[0253] Example 9 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (9) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 1 part by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (9). The results are shown in Table 1.
[0254] Example 10 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (10) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-554", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (10). The results are shown in Table 1.
[0255] Example 11 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (11) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 0.1 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (11). The results are shown in Table 1.
[0256] Example 12 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (12) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (12). The results are shown in Table 1.
[0257] Example 13 As shown in Table 1, the same procedure as in Example 1 was carried out except that the amount of fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the amount of ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.5 parts by weight, to obtain a surface protection film (13). The results are shown in Table 1.
[0258] Example 14 As shown in Table 1, the same procedure as in Example 1 was carried out except that the amount of fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, and the amount of ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was changed to 0.25 parts by weight, and an adhesive layer made of the adhesive composition (14) was produced, thereby obtaining a surface protection film (14). The results are shown in Table 1.
[0259] Example 15 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (15) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-551-A", manufactured by DIC) was changed to 1 part by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (15). The results are shown in Table 1.
[0260] Example 16 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (16) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-556", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (16). The results are shown in Table 1.
[0261] Example 17 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (17) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-551-A", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (17). The results are shown in Table 1.
[0262] Example 18 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (18) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-554", manufactured by DIC) was changed to 0.1 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (18). The results are shown in Table 1.
[0263] Example 19 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (19) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-563", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (19). The results are shown in Table 1.
[0264] Example 20 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (20) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 0.1 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (20). The results are shown in Table 1.
[0265] Example 21 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (21) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 2.0 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (21). The results are shown in Table 1.
[0266] Example 22 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (22) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 4.0 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (22). The results are shown in Table 1.
[0267] Example 23 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (23) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-553", manufactured by DIC) was changed to 6.0 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (23). The results are shown in Table 1.
[0268] Example 24 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (24) was produced in the same manner as in Example 1, except that the amount of fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 2.0 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (24). The results are shown in Table 1.
[0269] Example 25 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (25) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 4.0 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (25). The results are shown in Table 1.
[0270] Example 26 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (26) was produced in the same manner as in Example 1, except that the amount of the fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 6.0 parts by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (26). The results are shown in Table 1.
[0271] Example 27 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (27) was produced in the same manner as in Example 4, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 15.9 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (27). The results are shown in Table 1.
[0272] Example 28 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (28) was produced in the same manner as in Example 4, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 14.1 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (28). The results are shown in Table 1.
[0273] Example 29 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (29) was produced in the same manner as in Example 4, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 12.4 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (29). The results are shown in Table 1.
[0274] Example 30 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (30) was produced in the same manner as in Example 4, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 10.6 parts by weight in terms of solid content as shown in Table 1, and a surface protection film (30) was obtained. The results are shown in Table 1.
[0275] Example 31 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (31) was produced in the same manner as in Example 4, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 8.8 parts by weight in terms of solid content as shown in Table 1, and a surface protection film (31) was obtained. The results are shown in Table 1.
[0276] Example 32 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (32) was produced in the same manner as in Example 12, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 15.9 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (32). The results are shown in Table 1.
[0277] Example 33 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (33) was produced in the same manner as in Example 12, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 14.1 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (33). The results are shown in Table 1.
[0278] Example 34 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (34) was produced in the same manner as in Example 12, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 12.4 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (34). The results are shown in Table 1.
[0279] Example 35 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (35) was produced to obtain a surface protection film (35) in the same manner as in Example 12, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 10.6 parts by weight in terms of solid content as shown in Table 1. The results are shown in Table 1.
[0280] Example 36 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (36) was produced in the same manner as in Example 12, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 8.8 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (36). The results are shown in Table 1.
[0281] Example 37 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (37) was produced in the same manner as in Example 4, except that the amount of fluorine-based oligomer (product name "F-557", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, as shown in Table 1, to obtain surface protection film (37). The results are shown in Table 1.
[0282] Example 38 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (38) was produced in the same manner as in Example 37, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 15.9 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (38). The results are shown in Table 1.
[0283] Example 39 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (39) was produced in the same manner as in Example 37, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 14.1 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (39). The results are shown in Table 1.
[0284] Example 40 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (40) was produced in the same manner as in Example 37, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 12.4 parts by weight in terms of solid content as shown in Table 1, and a surface protection film (40) was obtained. The results are shown in Table 1.
[0285] Example 41 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (41) was produced in the same manner as in Example 37, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 10.6 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (41). The results are shown in Table 1.
[0286] Example 42 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (42) was produced in the same manner as in Example 37, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 8.8 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (42). The results are shown in Table 1.
[0287] Example 43 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (43) was produced in the same manner as in Example 8, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 15.9 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (43). The results are shown in Table 1.
[0288] Example 44 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (44) was produced in the same manner as in Example 8, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 14.1 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (44). The results are shown in Table 1.
[0289] Example 45 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (45) was produced in the same manner as in Example 8, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 12.4 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (45). The results are shown in Table 1.
[0290] Example 46 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (46) was produced in the same manner as in Example 8, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 10.6 parts by weight in terms of solid content as shown in Table 1, to obtain a surface protection film (46). The results are shown in Table 1.
[0291] Example 47 A pressure-sensitive adhesive layer made of pressure-sensitive adhesive composition (47) was produced to obtain surface protection film (47) in the same manner as in Example 8, except that the amount of the isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Industries, Ltd.) was changed to 8.8 parts by weight in terms of solid content as shown in Table 1. The results are shown in Table 1.
[0292] Example 48 100 parts by weight of urethane prepolymer A, 3 parts by weight of isocyanate compound (Coronate HX:C / HX, Nippon Polyurethane Co., Ltd.) as crosslinking agent, 0.5 parts by weight of Irganox1010 (BASF) as antioxidant, 1 part by weight of fluorine-based oligomer Megafac F-553 (DIC), 1 part by weight of 1-ethyl-3-methylimidazolium tri(fluoromethanesulfonyl)imide (AS110, Daiichi Kogyo Seiyaku Co., Ltd.) as ionic compound, diluted with ethyl acetate to a total solid content of 49% by weight to obtain a urethane-based adhesive solution. Then, the urethane-based adhesive solution was applied to a substrate (trade name "T100-75S", thickness 75 μm, Mitsubishi Chemical Co., Ltd.) made of polyester resin so that the thickness after drying was 75 μm, and cured and dried under conditions of a drying temperature of 120 ° C. and a drying time of 3 minutes to prepare an adhesive layer made of the adhesive composition (48). Next, the silicone-treated side of a release sheet (product name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of a 25 μm-thick polyester resin with one side silicone-treated was laminated to the surface of the obtained pressure-sensitive adhesive layer to obtain a surface protection film (48). Aging was carried out at room temperature for 5 days, and then evaluation was carried out. The release sheet was peeled off immediately before the evaluation. The results are shown in Table 1.
[0293] Example 49 A pressure-sensitive adhesive layer made of a pressure-sensitive adhesive composition (49) was produced in the same manner as in Example 48, except that the amount of the fluorine-based oligomer (product name "F-477", manufactured by DIC) was changed to 1.0 part by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (49). The results are shown in Table 1.
[0294] Example 50 A pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (50) was produced in the same manner as in Example 48, except that the amount of the fluorine-based oligomer (product name "F-557", manufactured by DIC) was changed to 1.0 part by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (50). The results are shown in Table 1.
[0295] Example 51 A pressure-sensitive adhesive layer made of a pressure-sensitive adhesive composition (51) was produced in the same manner as in Example 48, except that the amount of the fluorine-based oligomer (product name "F-559", manufactured by DIC) was changed to 1.0 part by weight in terms of solid content, as shown in Table 1, to obtain a surface protection film (51). The results are shown in Table 1.
[0296] Comparative Example 1 As shown in Table 1, the same procedure as in Example 1 was carried out except that 0.25 parts by weight of a fluorine-based oligomer (product name "F-569", manufactured by DIC) was used in terms of solid content, and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare an adhesive layer made of an adhesive composition (C1), and a surface protection film (C1) was obtained. The results are shown in Table 1.
[0297] Comparative Example 2 As shown in Table 1, the same procedure as in Example 1 was carried out except that 0.25 parts by weight of a fluorine-based oligomer (product name "F-553", manufactured by DIC) was used in terms of solid content, and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare an adhesive layer made of the adhesive composition (C2), and a surface protection film (C2) was obtained. The results are shown in Table 1.
[0298] Comparative Example 3 As shown in Table 1, the same procedure as in Example 1 was carried out except that 0.25 parts by weight of a fluorine-based oligomer (product name "F-477", manufactured by DIC) was used in terms of solid content, and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare an adhesive layer made of the adhesive composition (C3), and a surface protection film (C3) was obtained. The results are shown in Table 1.
[0299] Comparative Example 4 As shown in Table 1, the same procedure as in Example 1 was carried out except that 0.25 parts by weight of a fluorine-based oligomer (product name "F-551-A", manufactured by DIC) was used in terms of solid content, and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare an adhesive layer made of an adhesive composition (C4), and a surface protection film (C4) was obtained. The results are shown in Table 1.
[0300] Comparative Example 5 As shown in Table 1, except that the amount of the fluorine-based oligomer (product name "F-571", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, an adhesive layer made of the adhesive composition (C5) was produced in the same manner as in Example 1, and a surface protection film (C5) was obtained. The results are shown in Table 1.
[0301] Comparative Example 6 As shown in Table 1, except that the amount of the fluorine-based oligomer (trade name "F-552", manufactured by DIC) was changed to 0.25 parts by weight in terms of solid content, an adhesive layer made of the adhesive composition (C6) was produced in the same manner as in Example 1, and a surface protective film (C6) was obtained. The results are shown in Table 1.
[0302] Comparative Example 7 As shown in Table 1, except that no fluorine-based oligomer was used, a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (C7) was produced in the same manner as in Example 1, thereby obtaining a surface protective film (C7). The results are shown in Table 1.
[0303] Comparative Example 8 As shown in Table 1, the same procedure as in Example 1 was carried out except that no fluorine-based oligomer was used and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive composition (C8), and a surface protection film (C8) was obtained. The results are shown in Table 1.
[0304] Comparative Example 9 As shown in Table 1, the same procedure as in Example 48 was carried out except that no fluorine-based oligomer was used and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare a pressure-sensitive adhesive layer made of a pressure-sensitive adhesive composition (C9), and a surface protection film (C9) was obtained. The results are shown in Table 1.
[0305] Comparative Example 10 As shown in Table 1, the same procedure as in Example 49 was carried out except that no fluorine-based oligomer was used and no ionic compound (product name "AS110, manufactured by Dai-ichi Kogyo Seiyaku) was used, to prepare an adhesive layer made of the adhesive composition (C10), and to obtain a surface protection film (C10). The results are shown in Table 1.
[0306] Comparative Example 11 As shown in Table 1, except that the amount of the fluorine-based oligomer (trade name "F-571", manufactured by DIC) was changed to 1 part by weight in terms of solid content, an adhesive layer made of the adhesive composition (C11) was produced in the same manner as in Example 48, and a surface protection film (C11) was obtained. The results are shown in Table 1.
[0307] [Table 1]
[0308] [Examples 52 to 103] For each of the surface protection films (1) to (51) obtained in Examples 1 to 51, the separator was peeled off and the adhesive layer side was attached to a polarizing plate (manufactured by Nitto Denko Corporation, product name "TEG1465DUHC"), which is an optical component, to obtain an optical component with a surface protection film attached.
[0309] [Examples 104 to 155] For each of the surface protection films (1) to (51) obtained in Examples 1 to 51, the separator was peeled off and the adhesive layer side was attached to a conductive film (manufactured by Nitto Denko Corporation, product name "ELECRYSTA V270L-TFMP"), which is an electronic component, to obtain an electronic component with a surface protection film attached thereto. [Industrial Applicability]
[0310] The surface protective film of the present invention can be used for any suitable application, and is preferably used in the fields of optical members and electronic members. [Explanation of symbols]
[0311] 1 Base material layer 2 Adhesive layer 10 Surface protection film
Claims
1. A surface protection film including a pressure-sensitive adhesive layer, the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition, the pressure-sensitive adhesive composition comprises a base polymer, a polyfunctional isocyanate, an ionic compound, and an oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group; the base polymer is at least one selected from polyether polyols and polyurethane polyols, the oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group has a surface tension of 26.0 mN / m to 27.0 mN / m when made into a 0.1% toluene solution; the content of the oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group is 0.05 to 1.5 parts by weight based on 100 parts by weight of the base polymer, The surface free energy of the pressure-sensitive adhesive layer with respect to diiodomethane is 6 mJ / m 2 ~30mJ / m 2 That is, Surface protection film.
2. The surface protective film according to claim 1 , wherein the content of the ionic compound is 0.2 parts by weight or more based on 100 parts by weight of the base polymer.
3. The surface protection film according to claim 1 or 2, wherein the pressure-sensitive adhesive layer contained in the surface protection film is attached to a glass plate and left at a temperature of 23° C. for 30 minutes, and then the surface protection film is peeled off from the glass plate at a temperature of 23° C. at a peel angle of 180° and a peel speed of 300 mm / min. The peel force is 0.005 N / 25 mm to 0.1 N / 25 mm.
4. An optical member having the surface protective film according to claim 1 attached thereto.
5. An electronic component having the surface protective film according to claim 1 attached thereto.
Citation Information
Patent Citations
Antistatic treatment method
JP1997165460A
Surface protecting film and laminate using this film
JP2004223923A
Antistatic coating liquid composition and method for production thereof and antistatic coating film coated thereof
JP2008255332A
Dicing / die-bonding film and process for manufacturing semiconductor device
JP2010153774A
Surface protective film
JP2011063712A